Lithium-ion rechargeable battery
Patent Information
- Application Number
- JP2025225433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-17
- Filing Date
- 2025-12-03
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2039-12-04
AI Technical Summary
【0045】 本発明の一態様により、高容量で充放電サイクル特性に優れた、二次電池用正極活物質 、およびその作製方法を提供することができる。また、生産性のよい正極活物質の作製方 法を提供することができる。また、二次電池に用いることで、充放電サイクルにおける容 量の低下が抑制される正極活物質を提供することができる。また、高容量の二次電池を提 供することができる。また、充放電特性の優れた二次電池を提供することができる。また 、安全性又は信頼性の高い二次電池を提供することができる。また、新規な物質、活物質 粒子、蓄電装置、又はそれらの作製方法を提供することができる。
Smart Images

Figure 0007917688000008 
Figure 0007917688000009 
Figure 0007917688000010
Abstract
Description
Technical Field
[0001] One aspect of the present invention relates to an article, a method, or a manufacturing method. Alternatively, the present invention relates to a process , a machine, a manufacture, or a composition of matter . One aspect of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, or an electronic device, or a method for manufacturing the same. In particular, the present invention relates to a positive electrode active material that can be used for a secondary battery, a secondary battery, and an electronic device including the secondary battery.
[0002] Note that in this specification, the power storage device refers to all elements and devices having a power storage function . For example, it includes storage batteries (also referred to as secondary batteries) such as lithium ion secondary batteries, lithium ion ion capacitors, electric double layer capacitors, and the like.
[0003] In addition, in this specification, an electronic device refers to all devices including a power storage device, and all electro-optical devices including a power storage device, information terminal devices including a power storage device, and the like are electronic devices. Background Art
[0004] In recent years, various power storage devices such as lithium ion secondary batteries, lithium ion capacitors, and air batteries have been actively developed. In particular, lithium ion secondary batteries with high output and high energy density have been used in mobile phones, smartphones, tablets, notebook computers, and the like portable information terminals, portable music players, digital cameras, medical devices, next-generation clean energy vehicles (hybrid vehicles (HEV), electric vehicles (EV), plug-in hybrid vehicles (PHEV, etc.)), along with the development of the semiconductor industry, the demand for rechargeable As a source of energy, it has become indispensable in today's information society.
[0005] One of the characteristics required of lithium-ion secondary batteries is further increase in energy density. These improvements include enhanced cycle characteristics, safety in various operating environments, and improved long-term reliability.
[0006] Therefore, in order to improve the cycle characteristics and increase the capacity of lithium-ion secondary batteries, the positive electrode Improvements to the active material are being considered (Patent Documents 1 and 2). Also, the composition of the positive electrode active material Research on crystal structure has also been conducted (Non-Patent Documents 1 to 3).
[0007] X-ray diffraction (XRD) is one of the techniques used to analyze the crystal structure of positive electrode active materials. ICSD (Inorganic Crystal Str) is introduced in Non-Patent Document 5. By using a photo database, we can perform XRD data analysis. It is possible.
[0008] Furthermore, as shown in Non-Patent Documents 6 and 7, first-principles calculations can be used. This allows for the calculation of energy according to the crystalline structure, composition, etc., of a compound.
[0009] Patent Document 3 uses first-principles calculations to determine LiNi 1-x M x Calculate the inter-elemental distance of O2. Examples are shown. Furthermore, Patent Document 4 describes silicon oxide compounds obtained by first-principles calculations. The energy of creation is described. [Prior art documents] [Patent Documents]
[0010] [Patent Document 1] Special Announcement No. 2002-216760 [License 2] Special Announcement No. 2006-261132 [License 3] Special Announcement No. 2016-91633 [License 4] International Publication No. 2011 / 077654 [Non-licensed literature]
[0011] [Non-licensed Document 1] Toyoki Okumura et al, "Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation", Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-licensed Document 2] Motohashi, T. et al, "Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0) ", Physical Review B, 80(16), 2009, 165114 [Non-licensed Document 3] Zhaohui Chen et al, “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12) A1604-A1609 [Non-licensed Document 4] WE Counts et al, Journal of the American Ceramic Society, 1953, 36[1] 12-17. Fig.01471 [Non-licensed Document 5] Belsky, A. et al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., 2002, B58 364-369. [Non-Patent Document 6] Dudarev, SL et al, “Electron-energy-loss spectra and the structural stability of nickel oxide: An LSDA1U study”, Physical Review B, 1998, 57(3) 1505. [Non-Patent Document 7] Zhou, F. et al, “First-principles prediction of redox potentials in transition-metal compounds with LDA+U”, Physical Review B, 2004, 70 235121. [Overview of the project] [Problems that the invention aims to solve]
[0012] One aspect of the present invention provides a positive electrode active material for secondary batteries that has high capacity and excellent charge-discharge cycle characteristics. One of the objectives is to provide a method for producing a positive electrode active material with high productivity. This is one of the challenges. Alternatively, one aspect of the present invention, when used in a secondary battery, enables charging and discharging. One of the objectives is to provide a positive electrode active material that suppresses the decrease in capacity in the crust. One aspect of the present invention aims to provide a high-capacity secondary battery. One aspect of the invention aims to provide a secondary battery with excellent charge-discharge characteristics. One aspect of the present invention aims to provide a safe or highly reliable secondary battery. .
[0013] Alternatively, one aspect of the present invention relates to a novel substance, active material particles, energy storage device, or a method for producing the same. One of our objectives is to provide legal frameworks.
[0014] Furthermore, the description of these problems does not preclude the existence of other problems. One embodiment does not need to solve all of these problems. It is possible to extract other problems from the description of the claims. [Means for solving the problem]
[0015] One aspect of the present invention comprises lithium, cobalt, oxygen, and aluminum, and CuKα1 When Rietveld analysis is performed on a pattern obtained by linear powder X-ray diffraction, It has a crystal structure with an R-3m space group, and X-ray photoelectron spectroscopy analysis revealed aluminum It is a positive electrode active material whose number of atoms is 0.2 times or less the number of atoms of cobalt.
[0016] Furthermore, in the above configuration, the extraction angle in X-ray photoelectron spectroscopy is 40° or more and 50° or less. It is preferable.
[0017] Furthermore, in the above configuration, there is a field where particles are present and the cross-section of the particles is analyzed by TEM-EDX. In the first region where the distance from the surface of the particles is 20 nm or more and 200 nm or less Furthermore, in TEM-EDX analysis, the number of aluminum atoms is 0.0 times the number of cobalt atoms. The second type is one where the ratio is between 4 and 1.6, and the distance from the particle surface is between 1 μm and 3 μm. In this region, the number of aluminum atoms in TEM-EDX analysis is the same as the number of cobalt atoms. It is preferable that the number be less than 0.03 times the number.
[0018] Furthermore, in the above configuration, the cross-section of the particles is processed by a focused ion beam processing and observation device. It is preferable that it be exposed.
[0019] Furthermore, in the above configuration, the positive electrode active material has a coating that is in contact with the surface of the particles, and the coating is made of carbon The number of cobalt atoms in the coating is less than 0.05 times the number of carbon atoms in the coating. It is preferable to have one.
[0020] Furthermore, in the above configuration, magnesium is present, and in the analysis of X-ray photoelectron spectroscopy, the magnesium The number of cium atoms is preferably 0.4 to 1.5 times the number of cobalt atoms.
[0021] Alternatively, one aspect of the present invention relates to lithium, cobalt, oxygen, nickel, and aluminum The Rietveld solution is used to determine the pattern obtained by powder X-ray diffraction using CuKα1 rays. When analyzed, it was found to have a crystal structure with an R-3m space group, and X-ray photoelectron spectroscopy analysis was performed. Furthermore, aluminum has a lower atomic number than cobalt and a higher atomic number than nickel, making it a positive electrode active material.
[0022] Furthermore, in the above configuration, the extraction angle in X-ray photoelectron spectroscopy is 40° or more and 50° or less. It is preferable.
[0023] Furthermore, in the above configuration, there is a field where particles are present and the cross-section of the particles is analyzed by TEM-EDX. In the first region where the distance from the surface of the particles is 20 nm or more and 200 nm or less Furthermore, in TEM-EDX analysis, the number of aluminum atoms is 0.0 times the number of cobalt atoms. The second type is one where the ratio is between 4 and 1.6, and the distance from the particle surface is between 1 μm and 3 μm. In this region, the number of aluminum atoms in TEM-EDX analysis is the same as the number of cobalt atoms. It is preferable that the number be less than 0.03 times the number.
[0024] Furthermore, in the above configuration, in the first region, nickel is analyzed by TEM-EDX. The number of atoms is preferably less than 0.5 times the number of atoms of aluminum.
[0025] Furthermore, in the above configuration, the cross-section of the particles is processed by a focused ion beam processing and observation device. It is preferable that it be exposed.
[0026] Furthermore, in the above configuration, the positive electrode active material has a coating that is in contact with the surface of the particles, and the coating is made of carbon The number of cobalt atoms in the coating is less than 0.05 times the number of carbon atoms in the coating. It is preferable to have one.
[0027] Furthermore, in the above configuration, the sulfur concentration measured by glow discharge mass spectrometry is 150 pp. It is preferable that the m wt is between 2000 ppm wt and 3000 ppm wt.
[0028] Furthermore, in the above configuration, the titanium concentration measured by glow discharge mass spectrometry is 300p. It is preferable that the pm wt is less than or equal to 100%.
[0029] Another aspect of the present invention is an aggregate of particles having a first group of particles and a second group of particles. It contains lithium, cobalt, oxygen, and aluminum, and is used for powder X-ray irradiation with CuKα1 rays. When Rietveld analysis is performed on the patterns obtained by the process, the space group R-3m is It has a crystalline structure and is determined by elemental analysis by ICP-MS, GD-MS, or atomic absorption spectroscopy. The number of atoms in nesium is Mg1, and the number of atoms in cobalt is Co1, so Mg1 / Co1 is The particle size distribution of the first group of particles is between 0.001 and 0.06, and has a first maximum peak. Furthermore, the particle size distribution of the second group of particles has a second maximum peak, and the first maximum peak is 9 μm or smaller. The peak has a maximum value below 25 μm, and a second maximum peak is between 0.1 μm and 9 μm. It is a positive electrode active material that possesses [a certain characteristic].
[0030] Furthermore, in the above configuration, the intensity of the maximum value of the first maximum peak is defined as I1, and the intensity of the second maximum peak is defined as I1. Let I2 be the intensity of the maximum value of the function, and it is preferable that I1 / I2 be between 0.01 and 0.6. stomach.
[0031] Furthermore, in the above configuration, magnesium is present, and the aggregate of particles is analyzed by X-ray photoelectron spectroscopy. The number of magnesium atoms is between 0.4 and 1.5 times the number of cobalt atoms. It is preferable.
[0032] Furthermore, in the above configuration, the particle size distribution is measured using a laser diffraction particle size distribution analyzer. It is preferable to do so.
[0033] Furthermore, in the above configuration, the extraction angle in X-ray photoelectron spectroscopy is 40° or more and 50° or less. It is preferable.
[0034] Alternatively, one aspect of the present invention comprises a positive electrode having the positive electrode active material described in any one of the above, and a negative electrode The device has an electrolyte and performs one charge and one discharge cycle, and the first discharge capacity is determined from the discharge. After that, charge and discharge cycles were performed 50 times each, and the second discharge capacity was determined from the last discharge. This is a secondary battery whose discharge capacity is 90% or more than that of the first discharge capacity.
[0035] Furthermore, in the above configuration, charging is performed under CCCV conditions, and the CC charging current is 0.01C or less. The maximum current is 1.0C or less, and the upper limit voltage for CC charging is Li / Li + The standard is 4.55V or higher. The termination current for CV charging is 0.001C or higher, and discharge is performed under CC conditions, and CC discharge is performed. The current must be between 0.05C and 2.0C, and the measurement temperature must be between 15°C and 55°C. It is preferable.
[0036] Alternatively, one aspect of the present invention has a positive electrode having the positive electrode active material described in any one of the above, Using metallic lithium as the counter electrode, one charge and one discharge cycle were performed, and the first discharge capacity was obtained from the discharge. After determining the initial capacity, the battery is charged and discharged 50 times alternately, and the second discharge capacity is determined from the final discharge. The second discharge capacity is 90% or more of the first discharge capacity, and charging is performed under CCCV conditions. The CC charging current is between 0.01C and 1.0C, and the upper limit voltage for CC charging is Li / L i + The standard is 4.55V or higher, and the CV charging termination current is 0.001C or higher, and the discharge is The test was performed under CC conditions, with a CC discharge current of 0.05C to 2.0C, and the measurement temperature was This is a rechargeable battery that operates between 15°C and 55°C.
[0037] Alternatively, one aspect of the present invention relates to a composite oxide having lithium and cobalt, and aluminum The first step is to mix Um and to make a first mixture, and the second step is to heat the first mixture. The process comprises two steps, and in the first step, the aluminum contained in the first mixture The atomic ratio of cobalt in the composite oxide is aluminum:cobalt=C_a:1 This is a method for producing a positive electrode active material, where C_a is between 0.0005 and 0.02, expressed as follows.
[0038] Furthermore, in the above configuration, the heating temperature in the second step is 700°C to 920°C. The following is preferable:
[0039] Alternatively, one aspect of the present invention relates to a composite oxide having lithium and cobalt, and magnesium A first step of mixing um and fluorine to make a first mixture, and the first mixture A second step involves heating to produce a second mixture, and the second mixture, aluminum, A third step involves mixing to produce a third mixture, and a fourth step involves heating the third mixture. The third step has aluminum and the first In step, the atomic ratio of cobalt and aluminum in the composite oxide is aluminum:cobalt. Preparation of a positive electrode active material represented by =C_a:1, where C_a is between 0.0005 and 0.02. It is a method.
[0040] Furthermore, in the above configuration, the magnesium contained in the first mixture in the first step The atomic ratio of cobalt and magnesium in the composite oxide is magnesium:cobalt = C_m:1 It is expressed as follows, and it is preferable that C_m is between 0.001 and 0.06.
[0041] Furthermore, in the above configuration, the heating temperature in the fourth step is 700°C to 920°C. The following is preferable:
[0042] Alternatively, one aspect of the present invention relates to a composite oxide having lithium and cobalt, and magnesium A first step of mixing um and fluorine to make a first mixture, and the first mixture A second step involves heating to produce a second mixture, and the second mixture, aluminum, A third step involves mixing nickel and to produce a third mixture, and heating the third mixture. The fourth step is to have the third mixture having aluminum In the first step, the atomic ratio of cobalt and aluminum in the composite oxide is Mu:cobalt is expressed as C_a:1, where C_a is between 0.0005 and 0.02, and In step 3, the nickel contained in the third mixture, and in step 1, the composite acid The atomic ratio of cobalt and nickel in the ion is expressed as nickel:cobalt=C_n:1, and C_ This is a method for producing a positive electrode active material in which n is between 0.0005 and 0.02.
[0043] Furthermore, in the above configuration, the magnesium contained in the first mixture in the first step The atomic ratio of cobalt and magnesium in the composite oxide is magnesium:cobalt = C_m:1 It is expressed as follows, and it is preferable that C_m is between 0.001 and 0.06.
[0044] Furthermore, in the above configuration, the heating temperature in the fourth step is 700°C to 920°C. The following is preferable: [Effects of the Invention]
[0045] According to one aspect of the present invention, a positive electrode active material for secondary batteries has high capacity and excellent charge-discharge cycle characteristics. We can provide a method for producing the same. We can also provide a method for producing a positive electrode active material with high productivity. It can provide a method. Also, by using it in secondary batteries, it can provide capacity in charge-discharge cycles. This can provide a positive electrode active material in which the decrease in quantity is suppressed. Furthermore, it can provide a high-capacity secondary battery. It can be provided. Furthermore, it can provide a secondary battery with excellent charge and discharge characteristics. This enables the provision of safe and reliable secondary batteries. Furthermore, it allows for the development of novel materials and active materials. We can provide particles, energy storage devices, or methods for producing them. [Brief explanation of the drawing]
[0046] [Figure 1] Figures 1A and 1B illustrate an example of a cross-section of a positive electrode active material according to one embodiment of the present invention. [Figure 2] Figures 2A and 2B illustrate an example of a cross-section of a positive electrode active material according to one embodiment of the present invention. [Figure 3] Figure 3 illustrates an example of a cross-section of a positive electrode according to one embodiment of the present invention. [Figure 4] Figure 4 illustrates the charging depth and crystal structure of a positive electrode active material according to one embodiment of the present invention. [Figure 5] Figure 5 illustrates the charging depth and crystal structure of a conventional positive electrode active material. [Figure 6] Figure 6 shows the XRD pattern calculated from the crystal structure. [Figure 7] Figures 7A and 7B show the calculated relationship between lithium site occupancy and energy. [Figure 8] Figure 8 shows the calculation results of the relationship between lithium site occupancy and the c-axis. [Figure 9] Figure 9 shows the relationship between lithium site occupancy and the c-axis. [Figure 10] Figure 10 illustrates an example of a method for producing a positive electrode active material according to one embodiment of the present invention. [Figure 11] Figures 11A and 11B are cross-sectional views of the active material layer when a graphene compound is used as a conductive additive. [Figure 12] Figures 12A and 12B illustrate an example of a secondary battery according to one embodiment of the present invention. [Figure 13] Figures 13A and 13B illustrate an example of a secondary battery according to one embodiment of the present invention. [Figure 14] Figures 14A to 14C illustrate an example of a secondary battery according to one embodiment of the present invention. [Figure 15] Figures 15A and 15B illustrate an example of a secondary battery according to one embodiment of the present invention. [Figure 16]Figures 16A and 16B illustrate a coin-type rechargeable battery. Figure 16C illustrates the flow of electricity in a rechargeable battery. [Figure 17] Figures 17A and 17B illustrate a cylindrical secondary battery. Figures 17C and 17D illustrate a module having multiple cylindrical secondary batteries. [Figure 18] Figures 18A and 18B illustrate an example of a secondary battery. [Figure 19] Figures 19A to 19D illustrate examples of secondary batteries. [Figure 20] Figures 20A and 20B illustrate examples of secondary batteries. [Figure 21] Figure 21 illustrates an example of a secondary battery. [Figure 22] Figures 22A to 22C illustrate a laminate-type secondary battery. [Figure 23] Figures 23A and 23B illustrate laminate-type secondary batteries. [Figure 24] Figure 24 shows the external appearance of a secondary battery. [Figure 25] Figure 25 shows the external appearance of a secondary battery. [Figure 26] Figures 26A to 26C are diagrams illustrating the method for manufacturing a secondary battery. [Figure 27] Figures 27A to 27E illustrate a rechargeable battery that can be bent. [Figure 28] Figures 28A and 28B illustrate a rechargeable battery that can be bent. [Figure 29] Figures 29A and 29B illustrate an example of a secondary battery according to one embodiment of the present invention and a method for manufacturing the same. [Figure 30] Figures 30A to 30H illustrate an example of an electronic device. [Figure 31] Figures 31A to 31C illustrate an example of an electronic device. [Figure 32] Figure 32 illustrates an example of an electronic device. [Figure 33]Figures 33A to 33C illustrate an example of a vehicle. [Figure 34] Figure 34 shows the relationship between the battery's discharge capacity retention rate and discharge energy. [Figure 35] Figure 35 shows the relationship between the battery's discharge capacity retention rate and discharge energy. [Figure 36] Figure 36 shows the relationship between the battery's discharge capacity retention rate and discharge energy. [Figure 37] Figure 37 shows the relationship between the battery's discharge capacity retention rate and discharge energy. [Figure 38] Figures 38A and 38B show the results of the continuous battery charging test. [Figure 39] Figure 39 shows the evaluation results of XRD. [Figure 40] Figure 40 shows the evaluation results of XRD. [Figure 41] Figure 41 shows the evaluation results of the particle size distribution. [Figure 42] Figure 42 shows the cycle characteristics results. [Figure 43] Figure 43 shows the cycle characteristics results. [Figure 44] Figure 44 shows the evaluation results of the particle size distribution. [Figure 45] Figure 45 shows the cycle characteristics results. [Figure 46] Figure 46 shows the evaluation results of the particle size distribution. [Figure 47] Figure 47 shows the evaluation results of the particle size distribution. [Figure 48] Figure 48 shows the cycle characteristics of a secondary battery. [Modes for carrying out the invention]
[0047] The embodiments will be described below with reference to the drawings. However, many of the embodiments differ. It is possible to implement it in any manner, without deviating from its purpose and scope. It will be readily apparent to those skilled in the art that the details can be modified in various ways. Therefore, the present invention The following embodiments are not to be interpreted as being limited to their contents.
[0048] In this specification, the ordinal numbers "1st," "2nd," and "3rd" refer to the constituent elements. This is added to avoid confusion. Therefore, it does not limit the number of constituent elements. Furthermore, this does not limit the order of the components. Also, for example, the embodiments described herein The component referred to as "first" in one is in another embodiment or in the claims. It may also be the component referred to in "Second" in [the relevant section]. Furthermore, for example, in this specification, etc. In one embodiment, the component referred to as "first" is used in other embodiments, or It may be omitted in the claims.
[0049] In the drawings, elements that are identical or have similar functions, elements made of the same material, etc. In some cases, elements formed simultaneously may be given the same symbol, and the explanation for this repetition is as follows: It may be omitted in some cases.
[0050] Furthermore, in this specification, crystal planes and directions are indicated by Miller indices. In crystallography, numbers are represented with a superscript bar, but in this specification, due to limitations on patent application notation, the numbers are represented as follows: Sometimes, instead of placing a bar above a letter, a minus sign (-) is placed before the number to represent it. Furthermore, the individual orientations indicating directions within a crystal are [ ], and the collective orientation showing all equivalent directions is < > represents individual crystal planes ( ), and sets of planes with equivalent symmetry are {}. They express each other.
[0051] In this specification, segregation refers to the process of a solid composed of multiple elements (e.g., A, B, C). This refers to the phenomenon in which a certain element (for example, B) is distributed non-uniformly in space.
[0052] In this specification, the surface layer of particles such as active material refers to the region from the surface up to approximately 10 nm. This refers to the surface. Surfaces created by cracks or fissures can also be called the surface. Furthermore, the area deeper than the surface layer is also called the surface. , internally.
[0053] In this specification, etc., layered rock salt-type crystals of composite oxides containing lithium and transition metals The structure has a rock salt-type ionic arrangement in which cations and anions are arranged alternately, and transition metals Because lithium is arranged in a regular pattern to form a two-dimensional plane, two-dimensional diffusion of lithium is possible. This refers to a crystal structure. It may also have defects such as vacancies in cations or anions. Strictly speaking, a layered rock salt crystal structure is a structure in which the lattice of rock salt crystals is distorted. There is.
[0054] Furthermore, in this specification and elsewhere, a rock salt-type crystal structure is defined as a structure in which cations and anions are arranged alternately. This refers to a structure that is characterized by the presence of a cation or anion. A deficiency in either a cation or anion is also acceptable.
[0055] Furthermore, in this specification, etc., the pseudo-spinel type of composite oxide containing lithium and a transition metal The crystal structure of cobalt is space group R-3m, and although it is not a spinel-type crystal structure, it is cobalt Magnesium and other ions occupy the 6-coordinate position of oxygen, and the arrangement of cations is similar to that of a spinel. This refers to a crystal structure that possesses symmetry. Note that pseudo-spinel crystal structures are found in light elements such as lithium. The element may occupy the oxygen 4-coordinate position, and in this case as well, the ion arrangement is similar to that of the spinel type. It has symmetry.
[0056] Furthermore, the pseudo-spinel type crystal structure, although having Li randomly between layers, is a CdCl2 type. It can also be said that it is a crystal structure similar to the crystal structure. The crystal structure is when lithium nickelate is charged to a depth of charge of 0.94 (Li 0.06 Ni It has a crystal structure similar to that of O2, but is pure lithium cobaltate or a layered structure containing a large amount of cobalt. It is known that rock salt-type cathode active materials do not usually adopt this crystal structure.
[0057] Layered rock salt crystals, and the anions of rock salt crystals, have a cubic close-packed structure (face-centered cubic lattice structure). ) takes this form. It is also presumed that pseudo-spinel crystals adopt a cubic close-packed structure for anions. When they come into contact, there exists a crystal plane in which the orientation of the cubic close-packed structure composed of anions is aligned. However, the space group of layered rock salt crystals and pseudo-spinel crystals is R-3m, and rock salt The space groups of type crystals are Fm-3m (the space group of a typical rock salt type crystal) and Fd-3m (the simplest). Because it is different from the space group of rock salt crystals that have symmetry, the crystal planes that satisfy the above conditions The Lars index differs between layered rock salt crystals, pseudo-spinel crystals, and rock salt crystals. In layered rock salt crystals, pseudo-spinel crystals, and rock salt crystals, anions When the orientations of the cubic close-packed structures that are formed are aligned, we say that the crystal orientations are roughly the same. There is.
[0058] The approximate agreement of the crystal orientation in the two regions can be seen in TEM (transmission electron microscope) images and STE (spherical spectroscopy) images. M (Scanning Transmission Electron Microscope) image, HAADF-STEM (High-angle scattering annular dark-field scanning transmission electron microscope) image. The determination should be made based on images from a microscope, ABF-STEM (annular bright-field scanning transmission electron microscope), etc. This can be done. X-ray diffraction (XRD), electron diffraction, neutron diffraction, etc. can also be used as criteria for judgment. Yes, it is possible. In TEM images, the arrangement of cations and anions can be observed as a repetition of bright and dark lines. It can be inferred. When the orientation of the cubic close-packed structure is aligned in layered rock salt crystals and rock salt crystals, the crystal In between, the angle between the repetition of bright and dark lines is 5 degrees or less, more preferably 2.5 degrees or less. The condition can be observed. Furthermore, light elements such as oxygen and fluorine are clearly visible in TEM images, etc. In some cases, it may not be possible to discern this, but in such cases, the alignment of the metal elements can be determined by their arrangement. ru.
[0059] Furthermore, in this specification, the theoretical capacity of the positive electrode active material refers to the insertion and removal capacity of the positive electrode active material. This refers to the amount of electricity that would be generated if all the lithium were to be desorbed. For example, the theoretical capacity of LiCoO2 is 27 The theoretical capacity of LiNiO2 is 274mAh / g, and the theoretical capacity of LiMn2O4 is 4mAh / g. The capacity is 148mAh / g.
[0060] Furthermore, in this specification, etc., the charging depth when all insertable and removable lithium is inserted. The degree is 0, and the charge depth when all the insertable and detachable lithium in the positive electrode active material has been detached is 1. Let's assume that's the case.
[0061] Furthermore, in this specification, charging means moving lithium ions from the positive electrode to the negative electrode within the battery. This refers to the movement of electrons, specifically from the negative electrode to the positive electrode in an external circuit. Therefore, the process of releasing lithium ions is called charging. Also, the charging depth is 0.74 or higher. Positive electrode active material with a charge depth of 0.9 or less, more specifically 0.8 to 0.83, is subjected to high voltage. This refers to a charged positive electrode active material. Therefore, for example, in LiCoO2, 219 If it is charged at 0.2mAh / g, it is a positive electrode active material that has been charged at a high voltage. In O2, under a 25°C environment, the charging voltage is set to 4.525V or higher and 4.65V or lower (counter electrode lithium In the case of Um, constant current charging is performed, and then the current value is 0.01C, or the constant current charging value. The positive electrode active material, after being charged at a constant voltage until the current value is reduced to about 1 / 5 to 1 / 100, is also subjected to high voltage. This refers to a positive electrode active material that has been charged.
[0062] Similarly, discharge is the movement of lithium ions from the negative electrode to the positive electrode within a battery, and externally... This refers to the movement of electrons from the positive electrode to the negative electrode in a circuit. The positive electrode active material is lithium. The insertion of ions is called discharge. Also, the positive electrode active material has a charge depth of 0.06 or less, The positive electrode active material, which has been discharged to more than 90% of its charge capacity from a state of being charged at high voltage, This refers to the positive electrode active material that has been discharged for 2 minutes. For example, in LiCoO2, the charge capacity is 2 19.2mAh / g indicates a high-voltage charging state, and from here, 90% of the charge capacity... A positive electrode active material that has been discharged to a certain level of 197.3 mAh / g or more is a positive electrode active material that has been sufficiently discharged. It is of quality. Also, in LiCoO2, the battery voltage is 3V or less in a 25°C environment (counter electrode lithium In the case of Um, the positive electrode active material after constant current discharge until it reaches a certain state is also the positive electrode active material that has been sufficiently discharged. Let's assume that's the case.
[0063] Furthermore, in this specification, a non-equilibrium phase change refers to a phenomenon that causes a nonlinear change in a physical quantity. Let's assume that this is the case. For example, it can be obtained by differentiating capacitance (Q) with respect to voltage (V) (dQ / dV). Around the peaks in the dQ / dV curve, non-equilibrium phase transitions occur, and the crystal structure changes significantly. It is thought that they understand.
[0064] (Embodiment 1) This embodiment describes a positive electrode active material and the like according to one aspect of the present invention.
[0065] [Cathode active material] The discharge capacity of a secondary battery can be increased by increasing its charging voltage. If the active material has a crystalline structure, increasing the charging voltage will change that crystalline structure. There is a match.
[0066] If the change in crystal structure due to charging is irreversible, the positive electrode active material will change due to repeated charging and discharging. There are concerns that the crystal structure of the material may break down, leading to a decrease in discharge capacity.
[0067] As the charging voltage of a secondary battery increases, the voltage at the positive electrode generally increases. In one aspect of the present invention... The positive electrode active material has a stable crystal structure even at high voltages. During charging, the positive electrode active material The stable crystal structure suppresses the decrease in capacity that occurs with repeated charging and discharging. can.
[0068] Furthermore, a short circuit in a secondary battery can cause malfunctions in the charging and discharging operations of the secondary battery. This not only causes overheating but also the risk of fire. In order to realize safe rechargeable batteries, It is preferable that short-circuit current is suppressed even at high charging voltages. The extremely active material suppresses short-circuit current even at high charging voltages, providing high capacity and safety. It is possible to do both.
[0069] A secondary battery using a positive electrode active material according to one aspect of the present invention has high capacity and excellent charge / discharge cycle characteristics. It is preferable to satisfy both the requirements for performance and safety simultaneously.
[0070] Lithium cobalt oxide, lithium nickel-cobalt-manganate, nickel-cobalt - Positive electrode active materials having a layered structure, such as lithium aluminate, are used in secondary batteries. In the charging and discharging of the positive electrode active material, the amount of lithium per volume and per weight of the inserted and removed positive electrode active material is The amount of active material is extremely high. Therefore, secondary batteries using these positive electrode active materials have the advantage of high capacity. There is.
[0071] On the other hand, as the charging voltage increases, the positive electrode active material having a layered structure and carrier ions When a metal, more specifically lithium, is desorbed, a change in the lattice constant occurs. Alternatively, layer displacement may occur, making the crystal structure prone to collapse. For example, carrier ions and When a metal is located between layers, the desorption of the metal causes a change in the lattice constant perpendicular to the layer. This can occur quite noticeably.
[0072] A positive electrode active material according to one aspect of the present invention comprises a first metal (hereinafter referred to as metal A) and a second metal (hereinafter referred to as gold It is preferable that the metal A contains magnesium in addition to genus M and oxygen. Metal A is, for example, It is a metal that becomes a rear ion. Metal M is one or more metals that are responsible for the redox reaction. It is preferable that the positive electrode active material contains a metal. The inventors also prefer that the positive electrode active material contains magnesium. By adding luminium, the secondary voltage at higher voltages is improved compared to when other elements are added. We found that this suppresses battery short circuits.
[0073] While suppressing short circuits is desirable from a safety standpoint, it also reduces the discharge capacity. This can happen. For example, aluminum is effective in suppressing short-circuit currents, but There is a concern that if the concentration is too high, it may lead to a decrease in capacity. Here, the inventors considered the aforementioned magnesium And in a positive electrode active material having aluminum, by further adding nickel, Compared to adding other elements, the decrease in the discharge capacity of the secondary battery is suppressed more effectively. They discovered that.
[0074] In this case, if the positive electrode active material according to one aspect of the present invention has particles, then in the particles, It is preferable that the cium, aluminum, and nickel each have a concentration gradient, for example If the concentration near the surface is high, then it is preferable. On the other hand, nickel is magnesium and aluminum Compared to nium, nickel can sometimes be incorporated into particles at higher concentrations. In comparison, the magnesium and aluminum concentration gradients are biased towards the surface, resulting in a steeper gradient. In some cases, a file may have been present.
[0075] Here, a high charging voltage refers to, for example, 4.55V (vs Li / Li + ) The above, more preferable 4.6V (vs Li / Li + ) or more, more preferably 4.65V (vs Li / Li + That's all.
[0076] Metal A is, for example, alkali metals such as lithium, sodium, and potassium, and calcium. , elements from Group 2 such as beryllium and magnesium can be used, and lithium can be used as metal A. It is preferable to use M. Metal M is selected from, for example, cobalt, manganese, and iron. The above is preferable, and it is preferable that the metal M has cobalt. In addition to these elements Metal M may have one or more selected from nickel and manganese.
[0077] Examples of crystal structures of positive electrode active materials include layered rock salt type crystal structures and spinel type crystal structures. Examples include the structure and the olivine-type crystal structure. In particular, the positive electrode active material of one embodiment of the present invention The quality is preferably that it has a layered rock salt type crystalline structure. Furthermore, the layered rock salt type crystalline structure is air-filled. It is sometimes represented as the intergroup R-3m.
[0078] Let's consider the case where the positive electrode active material 100 has particles 101. Particles 101 are metal A, metal M, etc. It contains and oxygen. Particle 101 preferably contains magnesium and aluminum. In particle 101, it is preferable that magnesium and aluminum have a concentration gradient. It is preferable that, for example, the concentration near the surface of particle 101 is high. A high concentration in the surface layer is preferable.
[0079] For example, in particle 101, magnesium and aluminum are measured by XPS, etc. The concentration can be measured using ICP-MS (Inductively Coupled Plasma Mass Spectrometry) or GD-MS (Glow Radiation Spectrometry). It is preferable that the concentration is higher than that measured by electromass spectrometry or the like.
[0080] Furthermore, for example, in particle 101, magnesium and aluminum are processed When a cross-section is exposed and analyzed using TEM-EDX, the concentration in the surface layer is... It is preferable that the concentration is higher than that in the deeper regions. Processing is performed, for example, by FIB. It is possible.
[0081] Particle 101 preferably contains nickel. In particle 101, nickel is concentrated It is preferable that there is a gradient, for example, the concentration near the surface of particle 101 may be higher. In some cases, the concentration of particle 101 is high in the surface layer.
[0082] For example, in particle 101, the concentration of nickel is compared to the concentration measured by XPS, etc. The concentration measured by -MS or GD-MS may be higher.
[0083] Furthermore, for example, in particle 101, nickel exposes its cross-section through processing, and the cross-section is T When analyzing using EM-EDX, the concentration in the surface layer is compared to the concentration in deeper regions. Sometimes everything is expensive.
[0084] The magnesium, aluminum, and nickel contained in the positive electrode active material 100 are, for example, In some cases, a portion of the material may not be incorporated into the crystal structure. Incorporation into the crystal structure means... For example, the positive electrode active material 100 has a crystalline structure having metal A, metal M and oxygen, and the crystal In the structure, some of the elements in the crystal structure are magnesium, aluminum, and nickel. This refers to substitution of one or more of Kell's atoms. Alternatively, magnesium is substituted between the lattice of the crystal structure. Aluminum and nickel, or one or more of them, may be present.
[0085] The magnesium, aluminum, and nickel contained in the positive electrode active material 100 have a crystalline structure It does not need to be incorporated into the structure. Also, the positive electrode active material 100 is, for example, magnesium, The particles 102 may have luminium and nickel as the main components, or one or more. For example, particle 102 may be in contact with the surface of particle 101.
[0086] Particle 102 is, for example, at least one of magnesium, aluminum, and nickel. Its concentration is higher than that of the second metal.
[0087] Figure 1A shows an example of a cross-section of a particle 101 of the positive electrode active material 100. The particle 101 is It has regions 111 and 112.
[0088] As shown in Figure 1B, the distance x1 from the surface of particle 101 to region 111 is equal to the distance x1 from the surface of particle 101 It is smaller than the distance x 2 from the surface to region 112.
[0089] For example, the distance from the particle surface can be measured by the distance perpendicular to the tangent line to the surface of the particle's cross-section. This can be done. Alternatively, a line can be drawn from the surface of the particle cross-section to the center of the particle cross-section, or to the centroid. The distance in the direction can be used.
[0090] Figure 2A shows an example where distances in a different direction than those in Figure 1B are used.
[0091] When a secondary battery has a positive electrode, a negative electrode, and an electrolyte, the charging and discharging of the secondary battery involves electrolysis. The liquid decomposes, and the decomposed products become components of the electrode, such as particles 101 and particles of the active material. A coating 103 may be deposited on the surface of 102. Figure 2B shows the coating 10 on the surface of particle 101. An example of the accumulation of 3 is shown.
[0092] Figure 3 shows an example of a cross-section of a positive electrode. Figure 3 shows a positive electrode having particles 101 and 102. An example is shown in which the active material layer 109 is formed on the current collector 108. I will elaborate on this later.
[0093] When the number of cobalt atoms in the positive electrode active material 100 is set to 1, the number of magnesium atoms The relative value is preferably, for example, 0.001 or more and 0.06 or less, and 0.003 or more and 0.03 or less. More preferable. Also, when the number of cobalt atoms is set to 1, the relative value of the number of aluminum atoms is For example, a value of 0.0005 or more and 0.02 or less is preferred, and a value of 0.001 or more and 0.015 or less is more preferable. Preferably, 0.001 or more and more than 0.009 or less. (Assuming the number of cobalt atoms is 1) In this case, the relative value of the number of nickel atoms is preferably, for example, 0.0005 or more and 0.02 or less. 001 to 0.015 is more preferable, and 0.001 to 0.009 is even more preferable. i. The number of atoms in cobalt, magnesium, aluminum, and nickel The number of atoms can be evaluated, for example, by ICP-MS.
[0094] The particle size distribution of the positive electrode active material 100 has a maximum peak in the range of 9 μm to 25 μm. This is preferable. Alternatively, in the particle size distribution of the positive electrode active material according to one embodiment of the present invention, the average particle The diameter (D50) is preferably between 9 μm and 25 μm.
[0095] The particle size of the positive electrode active material 100 can be determined, for example, by surface observation using SEM, or by TEM. It can be evaluated using cross-sectional observation, etc. Furthermore, the particle size of the positive electrode active material 100 is It can be evaluated by particle size distribution. The particle size distribution of the positive electrode active material 100 is, for example, the laser rotation. It can be measured using a folding particle size distribution analyzer or the like.
[0096] Furthermore, if the maximum peak of the particle size distribution of the positive electrode active material 100 is between 9 μm and 25 μm: When the number of cobalt atoms in the positive electrode active material 100 is set to 1, the number of magnesium atoms The relative value is preferably, for example, 0.001 or more and 0.06 or less, and 0.003 or more and 0.03 or less. More preferably, 0.007 or more and 0.025 or less. The number of cobalt atoms and The number of magnesium atoms can be determined, for example, by ICP-MS.
[0097] The positive electrode active material 100 preferably contains a halogen such as fluorine.
[0098] In the positive electrode active material 100, the number of titanium atoms is, for example, 300 ppm wt or less.
[0099] The positive electrode active material 100 contains sulfur in an amount of 150 ppm wt or more and 2000 ppm wt or less. There are cases where this occurs.
[0100] The number of titanium atoms and sulfur atoms in the positive electrode active material 100 can be measured, for example, by GD-MS. It can be determined.
[0101] Furthermore, it is preferable that the positive electrode active material 100 is an aggregate of multiple particle groups with different particle size distributions. For details on each particle, please refer to the descriptions of particle 101 and particle 102 above, for example. It is possible.
[0102] If the positive electrode active material 100 is an aggregate of multiple particle groups with different particle size distributions, the particle size distribution is It is preferable to have a first maximum peak and a second maximum peak. The value is preferably, for example, 9 μm or more and 25 μm or less. The value of the second maximum peak is, for example, It is preferable that the thickness is 0.1 μm or more and less than 9 μm. Alternatively, the positive electrode active material 100 is first It has a first particle group and a second particle group, and in the particle size distribution of the first particle group, the average particle diameter ( D50) is preferably 9 μm or more and 25 μm or less, and the particle size distribution of the second group of particles is Furthermore, the average particle size (D50) is preferably 0.1 μm or more and less than 9 μm.
[0103] If the first and second maximum peaks overlap, use the function to determine the peak You may also perform separation and analyze the peak intensity and full width at half maximum of each peak.
[0104] The positive electrode active material 100 has multiple particle groups with different particle size distributions, In some cases, the density of the positive electrode active material layer using 00 can be increased. Increasing the density of the positive electrode active material layer can increase the amount of the active material per volume of the secondary battery. Therefore, the secondary batter y's capacity per volume may be increased in some cases. On the other hand, when the density of the positive electrode active material is high , there is a concern that the electrolytic solution is less likely to penetrate between the particles of the active material layer. In such a case, for example, there is a concern that the output characteristics of the secondary battery may deteriorate.
[0105] The positive electrode active material according to one aspect of the present invention is stable even at a high charging voltage, so the charging capacity can be increased , and as a result, the discharge capacity of the secondary battery can be increased. Therefore, even if the density of the positive electrode active material is not excessively increased, the capacity per volume of the secondary battery may be sufficiently high in some cases.
[0106] Furthermore, in the positive electrode active material layer, the proportion of materials other than the positive electrode active material, such as a conductive auxiliary agent and a binder, can be reduced , whereby the density of the positive electrode active material layer can be increased.
[0107] The thickness of the positive electrode active material layer is, for example, 10 μm or more and 200 μm or less. Alternatively, 50 μ m or more and 150 μm or less. For the loading amount of the positive electrode active material layer, for example, when the positive electrode active material includes a material having a layered rock salt type crystal structure containing cobalt , it is 1 mg / cm 2 or more and 50 mg / cm 2 or less. Alternatively, 5 mg / cm 2 or more and 30 mg / cm 2 or less. For a positive electrode active material layer, for example, when the positive electrode active material includes a material having a layered rock salt type crystal structure containing cobalt , the density is 2.2 g / cm 3 or more and 4.9 g / cm 3 or less. Alternatively, 3.8 g / cm3 More than 4.5g / cm 3 The following applies. Here, the amount of current carried is, for example, the positive electrode on one side of the current collector. This is the value for the active material layer.
[0108] <xps> X-ray photoelectron spectroscopy (XPS) can detect depths of approximately 2 to 8 nm (usually around 5 nm) from the surface. Since analysis of the region up to that point is possible, the concentration of each element can be determined for approximately half of the surface layer. It can be analyzed quantitatively. Furthermore, narrow-scan analysis can analyze the bonding state of elements. It is possible. Note that the quantitative accuracy of XPS is often around ±1 atomic percent, and the detection limit is for elements. It varies, but it's approximately 1 atomic percent. The unit of concentration in XPS is, for example, atomic percent.
[0109] When the positive electrode active material 100 has a first particle group and a second particle group, in the first particle group When the number of magnesium atoms is higher than the number of magnesium atoms in the second group of particles. There is.
[0110] Elemental analysis of the positive electrode active material 100 was performed using ICP-MS, GD-MS, or atomic absorption spectrometry. When the number of cobalt atoms (Co1) is set to 1, the number of magnesium atoms (Mg1) The relative value is preferably 0.4 or more and 1.5 or less, and more preferably 0.5 or more and 1.1 or less. The Mg1 / CO1 ratio is preferably between 0.001 and 0.06.
[0111] Furthermore, the relative number of atoms of halogens such as fluorine is preferably 0.05 or more and 1.5 or less, and 0.3 A value of 1.00 or less is more preferable.
[0112] Furthermore, when the positive electrode active material 100 was analyzed using XPS, the bonding energy between fluorine and other elements was observed. The peak indicating ghee is preferably between 682eV and less than 685eV, and ideally 684.8eV. It is even more preferable that it be around V. This is the bond energy of magnesium fluoride. This is a different value from 686 eV. In other words, if the positive electrode active material 100 contains fluorine, The bond is preferably a bond other than magnesium fluoride.
[0113] Further, when the positive electrode active material 100 is subjected to XPS analysis, a peak indicating the binding energy of a bond between magnesium and another element is preferably not less than 1302 eV and less than 1304 eV , and more preferably approximately 1303 eV. This is a value different from 1305 eV, which is the binding energy of magnesium fluoride, and close to the binding energy of magnesium oxide. In other words, when the positive electrode active material 100 contains magnesium, the bond of magnesium is preferably a bond other than magnesium fluoride.
[0114] In the positive electrode active material 100, the number of aluminum atoms evaluated by XPS may be lower than that of magnesium and higher than that of nickel. Further, when the number of cobalt atoms detected by XPS in the positive electrode active material 100 is defined as 1, the relative value of the number of aluminum atoms is, for example, 0.2 or less, or 0.15 or less. Nickel may not be detected by XPS after the heat treatment in the production method described later is performed.
[0115] Further, in the positive electrode active material according to one embodiment of the present invention, by performing the production method described later, the amount of carbonate-containing bonds may be reduced as compared with the composite oxide used in step S24.
[0116] <edx> EDX measurement is a method of measuring while scanning within a region and evaluating that region in two dimensions. This is sometimes called DX surface analysis. Furthermore, data from linear regions can be extracted from EDX surface analysis. The process of evaluating the distribution of atomic concentrations within positive electrode active material particles is sometimes called line analysis.
[0117] EDX surface analysis (e.g., elemental mapping) can be used to analyze the interior, surface, and vicinity of grain boundaries. Furthermore, the concentrations of magnesium and fluorine can be quantitatively analyzed. Also, EDX Linear analysis allows for the analysis of peak concentrations of magnesium and fluorine. ED The unit of concentration for X is, for example, atomic percent.
[0118] When EDX radiation analysis was performed on the particles 101 of the positive electrode active material 100, the particles 101 In the first region, where the distance from the surface is between 20 nm and 200 nm, EDX analysis was performed. The number of aluminum atoms is preferably 0.04 times or more and less than 1.6 times the number of cobalt atoms. Furthermore, in a second region where the distance from the surface of particle 101 is 1 μm or more and 3 μm or less, EDX analysis showed that the number of aluminum atoms is less than 0.03 times the number of cobalt atoms. preferable.
[0119] For a more specific EDX analysis method, for example, processing using FIB to expose the cross-section of the particles... One method is to extract the data and analyze it using TEM-EDX analysis.
[0120] [An example of the structure of a positive electrode active material] Figures 4 and 5 will be used to explain the positive electrode active material. This section describes the case where cobalt is used as the transition metal in a material.
[0121] The positive electrode active material shown in FIG. 5 is lithium cobalt oxide (LiCoO₂) to which halogen and magnesium are not added by the production method described later. As described in Non-Patent Document 1, Non-Patent Document 2, and the like, the crystal structure of the lithium cobalt oxide shown in FIG. 5 changes depending on the depth of charge.
[0122] As shown in FIG. 5, lithium cobalt oxide at a depth of charge of 0 (discharged state) has a region having a crystal structure of space group R-3m, and there are three CoO₂ layers in the unit cell. Therefore, this crystal structure is sometimes referred to as an O3-type crystal structure. The CoO₂ layer refers to a structure in which octahedral structures with 6-coordinate oxygen bonded to cobalt are continuously arranged on a plane in an edge-shared state.
[0123] When the depth of charge is 1, lithium cobalt oxide has a crystal structure of space group P-3m1, and there is one CoO₂ layer in the unit cell. Therefore, this crystal structure is sometimes referred to as an O1-type crystal structure.
[0124] When the depth of charge is about 0.88, lithium cobalt oxide has a crystal structure of space group R-3m This structure can be described as a structure in which a CoO₂ structure like that of P-3m1 (O1) and a LiCoO₂ structure like that of R-3m (O3) are alternately stacked. Therefore, this crystal structure is sometimes referred to as an H1-3-type crystal structure. Actually, in the H1-3-type crystal structure the number of cobalt atoms per unit cell is twice that of other structures. However, in FIG. 5 and throughout this specification, the c-axis of the H1-3-type crystal structure is shown as 1 / 2 of the unit cell to facilitate comparison with other structures.
[0125] As an example, the H1-3-type crystal structure is described in Non-Patent Document 3, where the unit cell has The coordinates of cobalt and oxygen are given as follows: Co(0, 0, 0.42150±0.00016), O 1(0, 0, 0.27671±0.00045), O2(0, 0, 0.11535±0. It can be represented as 00045). O1 and O2 are oxygen atoms, respectively. The H1-3 type crystal structure is formed by a unit cell consisting of one cobalt and two oxygen atoms. This is expressed. On the other hand, as will be described later, the pseudo-spinel type crystal structure of one aspect of the present invention is preferred. It is represented by a unit cell using one cobalt and one oxygen. This is a pseudo The symmetry between cobalt and oxygen differs between the spinel structure and the H1-3 type structure. The pseudo-spinel structure shows less variation from the O3 structure compared to the H1-3 type structure. This shows the crystal structure of the positive electrode active material. It is preferable to represent the crystal structure using any of the unit cells. The choice of , for example, in Rietveld analysis of XRD, GOF (good of You should choose the option that makes the fitness value smaller.
[0126] High-voltage charging such that the charging voltage is 4.6V or higher based on the oxidation-reduction potential of lithium metal. If you repeatedly charge to a deep depth of 0.8 or more, and then discharge the battery, Lithium cobalt oxide has an H1-3 type crystal structure and a R-3m(O3) structure in its discharged state. During this process, the crystal structure undergoes repeated changes (i.e., non-equilibrium phase transitions).
[0127] However, these two crystal structures have a large displacement of the CoO2 layer. (See dotted line in Figure 5) As indicated by the arrows, in the H1-3 type crystal structure, the CoO2 layer is large from R-3m(O3) It is collapsing. Such dynamic structural changes negatively affect the stability of the crystal structure. Eur.
[0128] Furthermore, the volume difference is also large. When comparing per the same number of cobalt atoms, H1-3 type crystal The difference in volume between the structure and the O3-type crystal structure in the discharged state is 3.0% or more.
[0129] In addition, the H1-3 type crystal structure has a continuous CoO2 layer, such as P-3m1(O1). The resulting structure is likely to be unstable.
[0130] Therefore, repeated high-voltage charging and discharging causes the crystalline structure of lithium cobalt oxide to break down. The breakdown of the crystal structure causes a deterioration in cycle properties. This reduces the number of sites where lithium can exist stably, and also makes lithium insertion and removal more difficult. This is likely the reason.
[0131] In one aspect of the present invention, the positive electrode active material undergoes repeated high-voltage charging and discharging, and the CoO2 layer This can be made smaller. Furthermore, the change in volume can be made smaller. Therefore, A positive electrode active material according to one aspect of the present invention can achieve excellent cycle characteristics. A positive electrode active material according to one aspect of the invention can adopt a stable crystalline structure in a high-voltage charged state. In one embodiment of the present invention, the positive electrode active material maintains a high-voltage charge state, In some cases, a reaction may be less likely to occur. In such cases, safety is further improved, which is preferable. .
[0132] In one embodiment of the present invention, the positive electrode active material is in a fully discharged state and a high-voltage charged state. In this case, the difference in volume when comparing the change in crystal structure and the same number of transition metal atoms is small.
[0133] An example of the crystal structure of the positive electrode active material 100 before and after charging and discharging is shown in Figure 4.
[0134] The crystal structure of the charge depth 0 (discharge state) in Figure 4 is R-3m(O3), the same as in Figure 5. On the other hand, when the positive electrode active material 100 is fully charged to a sufficient depth of charge, it has a different crystal structure from the H1-3 type. It has a crystal structure. This structure has a space group R-3m and is not a spinel-type crystal structure. In iron, ions such as cobalt and magnesium occupy the 6-coordinate position of oxygen, and the arrangement of cations It has symmetry similar to that of a spinel. Therefore, in this specification, this structure is referred to as a pseudo-spinel type. This is called the crystal structure. Note that in the diagram of the pseudo-spinel type crystal structure shown in Figure 4, the cobalt element The lithium atom is omitted from the diagram to explain the symmetry of the oxygen atom. However, in reality, there is less than 20 atomic percent lithium relative to cobalt between the CoO2 layers. Furthermore, in both the O3-type crystal structure and the pseudo-spinel-type crystal structure, the CoO2 layer It is preferable that a dilute amount of magnesium be present in between, that is, at the lithium site. It is preferable that halogens such as fluorine are present randomly and dilutely at the oxygen sites.
[0135] Furthermore, in pseudo-spinel crystal structures, light elements such as lithium occupy the oxygen 4-coordinate position. In this case as well, the arrangement of ions has a symmetry similar to that of the spinel type.
[0136] Furthermore, the pseudo-spinel type crystal structure, although having Li randomly between layers, is a CdCl2 type. It can also be said that it is a crystal structure similar to the crystal structure. The crystal structure is when lithium nickelate is charged to a depth of charge of 0.94 (Li 0.06 Ni It has a crystal structure similar to that of O2, but is pure lithium cobaltate or a layered structure containing a large amount of cobalt. It is known that rock salt-type cathode active materials do not usually adopt this crystal structure.
[0137] Layered rock salt crystals, and the anions of rock salt crystals, have a cubic close-packed structure (face-centered cubic lattice structure). ) takes this form. It is also presumed that pseudo-spinel crystals adopt a cubic close-packed structure for anions. When they come into contact, there exists a crystal plane in which the orientation of the cubic close-packed structure composed of anions is aligned. However, the space group of layered rock salt crystals and pseudo-spinel crystals is R-3m, and rock salt The space groups of type crystals are Fm-3m (the space group of a typical rock salt type crystal) and Fd-3m (the simplest). Because it is different from the space group of rock salt crystals that have symmetry, the crystal planes that satisfy the above conditions The Lars index differs between layered rock salt crystals, pseudo-spinel crystals, and rock salt crystals. In layered rock salt crystals, pseudo-spinel crystals, and rock salt crystals, anions When the orientations of the cubic close-packed structures that are formed are aligned, we say that the crystal orientations are roughly the same. There is.
[0138] In the positive electrode active material 100, when charged at high voltage and a large amount of lithium is released, the crystal structure The changes are more suppressed than in conventional positive electrode active materials. For example, as shown by the dotted line in Figure 4, In these crystal structures, there is almost no displacement of the CoO2 layer.
[0139] To explain in more detail, the positive electrode active material 100 maintains structural stability even at high charging voltages. It is expensive. For example, in the conventional positive electrode active material shown in Figure 5, the charging current has an H1-3 type crystal structure. Even at a voltage of approximately 4.6V, for example, with the potential of lithium metal as the reference, R-3m(O 3) There exists a region of charging voltage in which the crystal structure can be maintained, and further, a region where the charging voltage is increased, for example For example, even at a voltage of about 4.65V to 4.7V relative to the potential of lithium metal, pseudo-s There is a region where a Pinel-type crystal structure can be adopted. Furthermore, when the charging voltage is increased, H Type 1-3 crystals may be observed. Furthermore, in secondary batteries, for example, as a negative electrode active material... When using graphite, for example, even when the voltage of the secondary battery is between 4.3V and 4.5V, R There is a charging voltage range in which the -3m(O3) crystal structure can be maintained, and further increasing the charging voltage... In the range, for example, between 4.35V and 4.55V with the potential of lithium metal as the reference. There is also a region where a pseudo-spinel-type crystal structure can be adopted.
[0140] Therefore, in the positive electrode active material 100, the crystal structure does not collapse even when repeatedly charged and discharged at high voltage. It's hard to get.
[0141] In the pseudo-spinel type crystal structure, the coordinates of cobalt and oxygen in the unit cell are Co It can be shown that the coordinates are (0,0,0.5), O(0,0,x), and within the range 0.20≦x≦0.25. can.
[0142] Magnesium, which is randomly and dilutely present between the CoO2 layers, that is, at the lithium sites, It has the effect of suppressing the displacement of the CoO2 layer. Therefore, magnesium is present between the CoO2 layers. This makes it easy to form a pseudo-spinel type crystal structure. Therefore, magnesium is a positive electrode active material. It is preferable that magnesium is distributed throughout the entire particle. Therefore, it is preferable to perform a heat treatment in the process of manufacturing the positive electrode active material 100.
[0143] However, if the heat treatment temperature is too high, cation mixing occurs and magnesium The likelihood of magnesium entering the cobalt site increases. Furthermore, if the heat treatment temperature is too high, the effect of maintaining the structure of R-3m will be lost. There are concerns about adverse effects such as the reduction of cobalt to its divalent state and the evaporation of lithium. It can be done.
[0144] Therefore, prior to the heat treatment to distribute magnesium throughout the particles, cobalt acid It is preferable to add halogen compounds such as fluorine compounds to lithium. Adding a substance causes a decrease in the melting point of lithium cobalt oxide. By lowering the melting point, the At temperatures where on-mixing is unlikely to occur, it is easy to distribute magnesium throughout the particles. It is. Furthermore, if a fluorine compound is present, it provides corrosion resistance to hydrofluoric acid produced by the decomposition of the electrolyte. It can be expected that this will improve.
[0145] Furthermore, increasing the magnesium concentration beyond the desired value reduces its effect on stabilizing the crystal structure. In some cases, this can occur. Magnesium, in addition to lithium sites, also contains cobalt sites. This is thought to be because it will also be included in the "T" section.
[0146] <Charging method> For determining whether a certain composite oxide is a positive electrode active material 100 according to one aspect of the present invention High-voltage charging, for example, uses a coin cell (CR2032 type, 20mm diameter) with a lithium counter electrode. It can be made (3.2mm in diameter) and charged.
[0147] More specifically, the positive electrode consists of a slurry mixed with positive electrode active material, a conductive additive, and a binder. A positive electrode current collector made of aluminum foil can be used, coated with this material.
[0148] Lithium metal can be used as the counter electrode. However, if a material other than lithium metal is used as the counter electrode... When this occurs, the potential of the secondary battery and the potential of the positive electrode are different. Voltage and potential in this specification, etc. Unless otherwise specified, this represents the potential of the positive electrode.
[0149] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluoride phosphate (LiPF6). The electrolyte used is ethylene carbonate (EC) and diethyl carbonate (DEC). EC:DEC = 3:7 (volume ratio), vinylene carbonate (VC) is mixed at 2 wt%. You can use the one that you have.
[0150] Polypropylene with a thickness of 25 μm can be used for the separator.
[0151] The positive electrode and negative electrode cans can be made of stainless steel (SUS). Cut.
[0152] The coin cell manufactured under the above conditions was charged with a constant current of 4.6V and 0.5C, and then the current value was measured. Charge at a constant voltage until the current reaches 0.01C. Here, 1C is defined as 137mA / g. The temperature should be set to 25°C. After charging in this manner, the coin cell is subjected to an argon atmosphere glow. By disassembling the device in a box and removing the positive electrode, a positive electrode active material charged with high voltage can be obtained. To suppress reactions with external components when performing various analyses afterward, the area is sealed in an argon atmosphere. It is preferable to do so. For example, XRD can be performed by sealing the sample in a sealed container under an argon atmosphere. can.
[0153] <xrd> CuKα1 calculated from the pseudo-spinel type crystal structure and the H1-3 type crystal structure model. Figure 6 shows an ideal powder XRD pattern using lines. For comparison, a LiC with a charge depth of 0 is also shown. The ideal X calculated from the crystal structures of oO2(O3) and CoO2(O1) at a charge depth of 1 The RD pattern is also shown. Note that the patterns for LiCoO2(O3) and CoO2(O1) are as follows: ICSD(Inorganic Crystal Structure Database) e) From the crystal structure information obtained from (see Non-Patent Document 5), Materials Stud Reflex Powder Dif, one of the modules in io (BIOVIA) It was created using fraction. The range of 2θ was set to 15° to 75°, and Step s ize=0.01, wavelength λ1=1.540562×10 -10 m, λ2 not set, Mo The nochromator was set to single. The H1-3 type crystal structure pattern is unpatented. It was similarly created from the crystal structure information described in Reference 3. The pattern of the pseudo-spinel type crystal structure is The crystal structure of the positive electrode active material according to one embodiment of the present invention is estimated from the XRD pattern, and TOPAS ve The structure was fitted using r.3 (Bruker's crystal structure analysis software), and compared with others. Similarly, an XRD pattern was created.
[0154] As shown in Figure 6, in the pseudo-spinel type crystal structure, 2θ = 19.30 ± 0.20° (1 9.10° to 19.50°, and 2θ = 45.55 ± 0.10° (45.45 Diffraction peaks appear between 45.65° and 2θ. More specifically, 2θ = 19. 30±0.10° (19.20° to 19.40°), and 2θ = 45.55±0 A sharp diffraction peak appears at 0.05° (between 45.50° and 45.60°). However, H Peaks appear at these positions in the 1-3 type crystal structure and in CoO2 (P-3m1, O1). No. Therefore, when charged at high voltage, 2θ = 19.30 ± 0.20°, and 2 The appearance of a peak at θ = 45.55 ± 0.10° indicates that the positive electrode active material 1 of one embodiment of the present invention This can be considered a characteristic of 00.
[0155] This shows the crystal structure at a charging depth of 0 and the crystal structure when charged at high voltage, and the XRD diffraction peak It can also be said that the locations where the peaks appear are close together. More specifically, the main diffraction peaks of both. In two or more of these, more preferably three or more, the difference in the position where the peak appears is 2θ It can be said that 2θ = 0.7 or less, and more preferably 2θ = 0.5 or less.
[0156] In one embodiment of the present invention, the positive electrode active material 100, when charged with high voltage, forms a pseudo-spinel type crystal. Although it has a structure, not all particles have to have a pseudo-spinel type crystal structure. Other crystal structures It may contain or be partially amorphous. However, regarding the XRD pattern... When Rietveld analysis was performed, it was found that the pseudo-spinel type crystal structure was present in more than 50 wt% of the material. Preferably, it is 60 wt% or more, more preferably 66 wt% or more. Preferably, the pseudo-spinel crystal structure is present in an amount of 50 wt% or more, more preferably 60 wt% or more. More preferably, if the content is 66 wt% or more, it makes a positive electrode active material with sufficiently excellent cycle characteristics. It is possible.
[0157] Furthermore, Rietveld analysis was performed even after more than 100 charge-discharge cycles from the start of measurement. It is preferable that the pseudo-spinel crystal structure accounts for 35 wt% or more, and more preferably 40 wt% or more , and even more preferably 43 wt% or more.
[0158] Further, the crystallite size of the pseudo-spinel crystal structure contained in the particles of the positive electrode active material only decreases to about 1 / 10 of that of LiCoO2 (O3) in a discharged state . Therefore, even under the same XRD measurement conditions as for the positive electrode before charging and discharging , a distinct peak of the pseudo-spinel crystal structure can be confirmed after high-voltage charging. On the other hand, in simple LiCoO2, even if a part of it can adopt a structure similar to the pseudo-spinel crystal structure , the crystallite size becomes small, and the peak becomes broad and weak. , the crystallite size becomes small, and the peak becomes broad and weak. The crystallite size can be obtained from the half width of the XRD peak.
[0159] <dQ / dV vs V curve> Further, when the positive electrode active material according to one embodiment of the present invention is discharged at a low rate of, for example, 0.2 C or less after being charged at a high voltage , a characteristic voltage change may appear near the end of discharge. This change can be clearly confirmed by the presence of at least one peak in the range from 3.5 V to 3.9 V in the dQ / dV vs V curve obtained from the discharge curve can be clearly confirmed by the presence of at least one peak in the range from 3.5 V to 3.9 V in the dQ / dV vs V curve obtained from the discharge curve.
[0160] [First-principles calculation] Next, how the stability of the crystal structure and the like change with the addition of magnesium to the positive electrode active material according to one embodiment of the present invention was estimated by first-principles calculation.
[0161] For the aforementioned O3-type crystal structure and H1-3-type crystal structure, the change in energy when lithium is desorbed from each structure was calculated using first-principles calculation. In addition, for each crystal Regarding the case where 2% of the lithium in the lithium sites is replaced with magnesium in the structure: I also performed the calculations.
[0162] The lattice and atomic positions were optimized using first-principles calculations, and the energy was determined. VASP (The Vienna Ab initio simulatio) The n package was used as the functional. Additionally, LDA (Local Density Approximation) was used. The density approximation (U) was used. The value was set to 4.91. The pseudopotential of the electronic state is PAW (Projector Au The potential generated by the (gmented wave) method was used. Energy was set to 600 eV. k-points were sampled using a 1x1x1 mesh. For information on the U potential, please refer to Non-Patent Documents 6 and 7. .
[0163] The number of atoms used in the calculation is (48-x) lithium atoms in the case without magnesium addition. If there are 48 cobalt atoms and 96 oxygen atoms, and magnesium is added, then lithium will be (47- x) atoms, 1 magnesium atom, 48 cobalt atoms, and 96 oxygen atoms. x is the atom that was removed. This is the number of lithium atoms.
[0164] In this specification, the energy obtained in this manner is referred to as the stabilization energy. There is.
[0165] From a crystal structure model in which one magnesium atom is substituted at a lithium site, x lithium atoms are removed. The energy difference ΔE of the resulting crystal structure model can be calculated using the following equation 1. .
[0166]
number
[0167] Here E total (Li 47 Mg1Co 48 O 96 ) is Li 48 Co 48 O 96 No Rich The energy of the structure in which one um atom is replaced by Mg is E total (Li 47-x Mg1C o 48 O 96 ) is Li 48 Co 48 O 96 By substituting one lithium atom with Mg, The energy of a structure in which x atoms have been removed is E. atom (Li) is the energy of one lithium atom Rugie, E atom (Co) represents the energy of one cobalt atom, E atom (Mg) is This is the energy of one magnesium atom. Furthermore, equation 1 above represents the energy of one lithium atom. This is a crystal structure model in which um atoms are substituted, but lithium atoms are substituted with magnesium atoms. The same calculations were performed for models that did not exist.
[0168] The calculation results are shown in Figures 7 and 8.
[0169] In Figure 7A, the horizontal axis represents the lithium site occupancy rate, and the vertical axis represents the energy difference ΔE. Figure 7B shows... As shown by the dashed line in Figure 7A, the energy difference ΔE is 6 eV when the lithium site occupancy rate is 0%. This figure plots the difference between the straight line and the calculation result on the vertical axis. The positive result is obtained by charging the secondary battery. The lithium, the most active material, is desorbed. Therefore, the energy lost when the occupancy rate of the lithium sites decreases. By calculating the ghee, we can consider the state in which lithium has been desorbed due to charging. .
[0170] As shown in Figures 7A and 7B, when the occupancy rate of lithium sites decreases, the energy difference ΔE increases, and the crystal structure becomes unstable. Also, as can be seen from Figure 7B, the O3 type crystal structure It is suggested that the energies of the structure and the H1-3 type crystal structure intersect, and that a phase change occurs at the intersection. In structures where magnesium is substituted with one atom, the O3 type crystal structure and the H1-3 type crystal structure are observed. The occupancy rate of lithium sites where the intersection of structures is observed is in structures that do not have magnesium substitution. It is comparatively lower. In other words, it is possible to desorb more lithium without a phase change occurring. This suggests that...
[0171] The calculation results shown in Figures 7A and 7B indicate that adding magnesium increases the concentration. This can be said to stabilize the charging of the positive electrode active material under electrical voltage.
[0172] In Figure 8, the horizontal axis represents the lithium site occupancy rate, and the vertical axis represents the lattice constant (c-axis). As the occupancy rate decreased, the lattice constant of the c-axis increased, and then subsequently decreased.
[0173] Figure 9 shows the c-axis values calculated from measured XRD values for a positive electrode active material according to one embodiment of the present invention. This shows the relationship with the lithium site occupancy rate. Here, the theoretical capacity of lithium cobalt oxide is 27 The value was set to 4 mAh / g. Figure 9 shows agreement between the calculated result and the observed phenomenon.
[0174] This embodiment can be implemented in appropriate combination with other embodiments.
[0175] (Embodiment 2) This embodiment shows an example of a method for producing a positive electrode active material according to one aspect of the present invention.
[0176] [An example of a method for preparing positive electrode active material] Next, an example of a method for producing a positive electrode active material according to one embodiment of the present invention will be described using Figure 10. ru.
[0177] <Step S11> In step S11, first, the materials of mixture 902 are halogens such as a fluorine source and a chlorine source. Prepare a magnesium source and a lithium source. A lithium source may also be provided.
[0178] For example, lithium fluoride and magnesium fluoride can be used as fluorine sources. In particular, lithium fluoride has a relatively low melting point of 848°C, and in the annealing process described later... It is preferable because it melts easily. Examples of chlorine sources include lithium chloride and magnesium chloride. Magnesium sources can be used, for example, magnesium fluoride, magnesium oxide. Lithium, magnesium hydroxide, magnesium carbonate, etc. can be used. For example, lithium fluoride and lithium carbonate can be used. Lithium can be used as both a lithium source and a fluorine source. Cium can be used as both a fluorine source and a magnesium source.
[0179] In this embodiment, lithium fluoride (LiF) is prepared as the fluorine source, and the fluorine source and Magnesium fluoride (MgF2) will be used as the magnesium source. Lithium fluoride LiF and magnesium fluoride (MgF2) have a molar ratio of approximately LiF:MgF2 = 65:35. Mixing them in this way yields the greatest effect in lowering the melting point (Non-Patent Document 4). On the other hand, lithium fluoride If the amount increases, there is a concern that lithium will become excessive and the cycle characteristics will deteriorate. The molar ratio of lithium fluoride (LiF) to magnesium fluoride (MgF2) is LiF:MgF2 = It is preferable that x:1 (0≦x≦1.9), and LiF:MgF2=x:1 (0.1≦ (x ≤ 0.5) is more preferable, and LiF:MgF2 = x:1 (near x = 0.33) is even more preferable. Preferred. In this specification, "nearby" means greater than 0.9 times the value and greater than 1.1 times the value. Set it to a small value.
[0180] Furthermore, if the following mixing and grinding steps are to be performed wet, a solvent will be prepared. The solvent will be A Ketones such as cetone, alcohols such as ethanol and isopropanol, ethers, and dio Xane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that does not react easily with lithium. In this embodiment, acetone will be used.
[0181] <Step S12> Next, as step S12, the materials of the above mixture 902 are mixed and ground. This can be done dry or wet, but wet grinding is preferred because it allows for finer grinding. It seems. For mixing, for example, a ball mill, bead mill, etc. can be used. When used, it is preferable to use zirconia balls as the media, for example. It is preferable to thoroughly perform the blending and grinding processes to finely pulverize the mixture 902.
[0182] <Step S13> Next, in step S13, the materials mixed and crushed above are recovered, and the mixture 902 is prepared obtain.
[0183] Mixture 902, for example, has an average particle size (D50) of 600 nm or more and 20 μm or less. It is preferable that the particle size is 1 μm or more and 10 μm or less. If the mixture 902 is used, a composite oxide having lithium, a transition metal and oxygen can be obtained in a later step. When mixed with the composite oxide particles, the mixture 902 adheres uniformly to the surface of the composite oxide particles. When the mixture 902 is uniformly attached to the surface of the composite oxide particles, the composite oxide particles are heated. This is preferable because it allows for the even distribution of halogens and magnesium throughout the surface layer. If there is a region that does not contain halogen and magnesium, the aforementioned pseudo-s There is a risk that it may not form a Pinel-type crystal structure.
[0184] Next, through steps S21 to S24, metal A, metal M and oxygen A composite oxide is obtained.
[0185] <Step S21> First, in step S21, a composite oxide material having metal A, metal M, and oxygen is used. Next, prepare metal source A and metal source M.
[0186] Let's explain an example using lithium as metal A. A lithium source could be, for example, carbonic acid. Lithium, lithium fluoride, etc., can be used.
[0187] For example, at least one of cobalt, manganese, and nickel can be used as the metal M. can.
[0188] When using a layered rock salt crystal structure as the positive electrode active material, the ratio of the materials is as follows: The mixture ratio of cobalt, manganese, and nickel should be appropriate. Also, the layered rock salt crystal structure is suitable. Aluminum may be added to these transition metals to the extent that it is possible.
[0189] As the source of metal M, oxides, hydroxides, etc. of the above-mentioned metals are used as examples of metal M. This can be done. As a cobalt source, for example, cobalt oxide, cobalt hydroxide, etc. can be used. Yes, it is possible. Manganese oxide, manganese hydroxide, etc., can be used as manganese sources. Nickel oxide, nickel hydroxide, etc. can be used as nickel sources. Aluminum oxide, aluminum hydroxide, and the like can be used as the um source.
[0190] <Step S22> Next, in step S22, the above metal source A and metal source M are mixed. The mixing is done dry. Alternatively, it can be done wet. For mixing, for example, a ball mill or bead mill can be used. Yes, it is possible. When using a ball mill, for example, zirconia balls can be used as the media. This is preferable.
[0191] <Step S23> Next, in step S23, the mixed materials are heated. This step is a subsequent heating step. To distinguish it from other processes, it is sometimes referred to as firing or first heating. Heating is performed at 800°C or higher and 110°C. It is preferable to carry out the process at a temperature below 0°C, and more preferably at a temperature between 900°C and 1000°C. A temperature of around 950°C is even more preferable. If the temperature is too low, the decomposition and melting of the starting material will be insufficient. There is a risk of it becoming a minute. On the other hand, if the temperature is too high, the oxidation-reduction reaction will occur when using metal M. Defects may occur due to excessive reduction of the metal or evaporation of metal A. For example, if cobalt is used as the metal M, defects in which the cobalt becomes divalent may occur.
[0192] The heating time is preferably between 2 hours and 20 hours. The firing process involves using dry air or other moisture-free materials. This process should be carried out in an atmosphere with low humidity (for example, a dew point of -50°C or lower, more preferably -100°C or lower). Preferably, heating at 1000°C for 10 hours, with the temperature increase at 200°C / h, and drying The atmosphere flow rate is preferably 10 L / min. After that, the heated material is cooled to room temperature. It can be rejected. For example, if the cooling time from the specified temperature to room temperature is 10 hours or more and 50 hours or more It is preferable to place it at the bottom.
[0193] However, cooling to room temperature in step S23 is not mandatory. If there are no problems in carrying out steps 24 and S31 to S33, then cooling will It may be limited to temperatures higher than room temperature.
[0194] Regarding the metal contained in the positive electrode active material, the above steps S22 and S2 It may be introduced in step 3, and for some of the metals, steps S41 to S described later may be used. It can also be introduced in step S44. More specifically, in step S22 and In step S23, metal M1 (M1 is cobalt, manganese, nickel, and aluminum) Introduce one or more selected from M, and in steps S41 to S44, metal M2 (M2 is, for example, one or more selected from manganese-nickel and aluminum) In this way, by separating the process of introducing metal M1 and metal M2, each metal It may be possible to change the profile in the depth direction. For example, compared to the interior of a particle. This allows for an increase in the concentration of metal M2 in the surface layer. Furthermore, using the number of atoms of metal M1 as a reference, The ratio of the number of metal M2 atoms to the standard is made higher in the surface layer than in the interior. It is possible.
[0195] In one embodiment of the present invention, in a positive electrode active material, cobalt is preferably selected as the metal M1. Nickel and aluminum are selected as metal M2.
[0196] <Step S24> Next, in step S24, the material that was calcined above is recovered, and metal A, metal M and oxygen A composite oxide having the following is obtained. Specifically, lithium cobaltate, lithium manganeseate, and Lithium cobaltate, lithium cobaltate in which some of the cobalt is replaced by manganese, or This yields lithium nickel-manganese-cobalt oxide, etc.
[0197] Furthermore, step S24 includes pre-synthesized metal A, metal M, and oxygen A composite oxide may be used. In this case, steps S21 to S23 may be omitted. It is possible.
[0198] For example, as a pre-synthesized composite oxide, cobalt manufactured by Nippon Chemical Industrial Co., Ltd. Lithium oxide particles (product name: Cellseed C-10N) can be used. These are average particle sizes. The particle size (D50) is approximately 12 μm, and impurities were detected by glow discharge mass spectrometry (GD-MS). In the analysis, magnesium and fluorine concentrations were 50 ppm wt or less, and calcium The concentration, aluminum concentration, and silicon concentration are 100 ppm wt or less, and the nickel concentration is Sulfur concentration of 150 ppm wt or less, sulfur concentration of 500 ppm wt or less, arsenic concentration of 1100 ppm m wt or less, and the concentration of elements other than lithium, cobalt, and oxygen is 150 ppm. This is lithium cobalt oxide with a wt value of less than or equal to 1 wt.
[0199] Alternatively, lithium cobalt oxide particles manufactured by Nippon Chemical Industrial Co., Ltd. (product name: Cellseed C- 5H) can also be used. This has an average particle size (D50) of approximately 6.5 μm, and GD -In impurity analysis by MS, the concentrations of elements other than lithium, cobalt, and oxygen were C- This is lithium cobalt oxide, equivalent to or less than 10N.
[0200] In this embodiment, cobalt is used as the metal M, and pre-synthesized cobalt oxide is used. We will use thium particles (Cellseed C-10N, manufactured by Nippon Chemical Industrial Co., Ltd.).
[0201] <Step S31> Next, in step S31, the mixture 902 and the composite oxide obtained in step S24 Mix ,. Number of atoms of transition metal in a composite oxide containing lithium, transition metal and oxygen. The ratio of TM to the number of magnesium atoms in mixture 902 (MgMix1) is TM:Mg It is preferable that Mix1 = 1:y (0.001 ≤ y ≤ 0.06), and TM:MgMi It is more preferable that x1 = 1 and y (0.003 ≤ y ≤ 0.03).
[0202] The mixing in step S31 is performed in order to avoid destroying the composite oxide particles, as is the case with the mixing in step S12. It is preferable to use milder conditions. For example, a higher rotational speed than the mixing in step S12. It is preferable to have conditions with less or shorter duration. Also, dry processing is gentler than wet processing. It can be said that these are favorable conditions. For mixing, for example, a ball mill or bead mill can be used. To do so. When using a ball mill, for example, zirconia balls can be used as the media. It is preferable.
[0203] <Step S32> Next, in step S32, the materials mixed above are collected to obtain mixture 903.
[0204] In this embodiment, the mixture of lithium fluoride and magnesium fluoride is treated as an impurity. Although a method of adding to lithium cobalt oxide with low concentration is described, one aspect of the present invention is This is not the only option. Instead of mixture 903 in step S33, lithium cobalt oxide is used as the starting material. You may also use materials that have been calcined with added magnesium and fluorine sources. This includes the process of steps S11 to S14 and steps S21 to S24. Because there is no need to separate the processes, it is simple and highly productive.
[0205] Alternatively, lithium cobalt oxide with pre-added magnesium and fluorine can be used. It may also be used. If lithium cobalt oxide with magnesium and fluorine added is used, Steps up to S32 can be omitted, making the process simpler.
[0206] Furthermore, lithium cobalt oxide, which has magnesium and fluorine added to it beforehand, Furthermore, a magnesium source and a fluorine source may be added.
[0207] <Step S33> Next, in step S33, the mixture 903 is heated. This step is separate from the previous heating step. For other reasons, this may be called annealing or a second heating.
[0208] Annealing is preferably carried out at an appropriate temperature and time. The size of the particles of the composite oxide having lithium, transition metal and oxygen in step S24 It varies depending on conditions such as composition. If the particles are small, a lower temperature or Shorter durations may be preferable in some cases.
[0209] For example, if the average particle size (D50) of the particles in step S24 is about 12 μm, annealing The temperature is preferably between 600°C and 950°C. The annealing time is, for example, 3 hours or more. Preferably, 10 hours or more is preferred, more preferably 60 hours or more.
[0210] On the other hand, if the average particle size (D50) of the particles in step S24 is about 5 μm, the annealing temperature The temperature is preferably between 600°C and 950°C. The annealing time is, for example, between 1 hour and 10 hours. Less than 1 hour is preferable, and around 2 hours is more preferable.
[0211] The cooling time after annealing is preferably, for example, 10 hours or more and 50 hours or less.
[0212] If the annealing temperature is too high in step S33, the particles may sinter.
[0213] When mixture 903 is annealed, first the material with the lower melting point from mixture 902 (for example, fluorine) It is thought that lithium oxide (melting point 848°C) melts and is distributed on the surface of the composite oxide particles. Next, the presence of this molten material causes a decrease in the melting point of other materials, which in turn causes the other materials to melt. It is presumed that, for example, magnesium fluoride (melting point 1263°C) melts and becomes a composite oxide. It is thought to be distributed on the surface layer of the particles.
[0214] The elements present in the mixture 902 distributed on the surface are lithium, transition metals, and oxygen. It is thought to form a solid solution in a composite oxide containing [the specified element].
[0215] The elemental diffusion of this mixture 902 occurs more in the surface layer and within the composite oxide particles than within the composite oxide particles. The reaction is faster near grain boundaries. Therefore, magnesium and halogens are concentrated in the surface layer and near grain boundaries. As described later, the magnesium concentration in the surface layer and near the grain boundaries is higher than in the interior. When the value is high, changes in the crystal structure can be suppressed more effectively.
[0216] <Step S34> Next, in step S34, the material annealed above is recovered to obtain a second composite oxide. .
[0217] Next, the composite oxide obtained in step S34 is subjected to further treatment. Here, gold A process is performed to add M2. This process is performed after step S24. This allows the concentration of metal M2 in the particle surface layer of the positive electrode active material to be higher than in the interior. In some cases, this is preferable.
[0218] Furthermore, the addition of metal M2 is, for example, in step S31, together with the mixture 902, etc. This may be done by mixing materials containing M2. In this case, the number of steps can be reduced and the process can be simplified. It is preferable because it can be converted into a liquid.
[0219] Alternatively, as will be explained below, after steps S31 to S33, the metal M2 An additive step may be performed. In this case, for example, the formation of a compound of magnesium and metal M2. It may be possible to suppress it.
[0220] The positive electrode active material of one aspect of the present invention is obtained through the following steps S41 to S43. Next, metal M2 is added. The addition of metal M2 can be done, for example, by liquid methods such as the sol-gel method. Phase method, solid-phase method, sputtering method, vapor deposition method, CVD (chemical vapor deposition), PLD (pulse deposition) Methods such as laser deposition can be applied.
[0221] <Step S41> First, in step S41, prepare the metal source. Also, when applying the sol-gel method... This involves preparing the solvent to be used in the sol-gel method. The metal sources include metal alkoxides and metal water. Oxides, metal oxides, etc. can be used. For example, if metal M2 is aluminum... If we consider the number of cobalt atoms in lithium cobalt oxide as 1, and the number of aluminum atoms in the metal source as 1 The relative number of atoms in M should be between 0.005 and 0.02. In cases where nickel is present in addition to mu, for example, the cobalt found in lithium cobalt oxide With the number of atoms set to 1, the relative value of the number of nickel atoms in the metal source is between 0.0005 and 0.02. It should be at the bottom.
[0222] Here, as an example, the sol-gel method is applied, and aluminum isopropone is used as the metal source. An example using isopropanol as the solvent for the side is shown (Step S41 in Figure 10).
[0223] <Step S42> Next, in step S42, the aluminum alkoxide is dissolved in alcohol, and Lithium cobalt oxide particles are mixed into it.
[0224] Next, a mixture of an alcoholic solution of metal alkoxide and lithium cobalt oxide particles is added to water. Stir in a steam-containing atmosphere. Stirring can be done, for example, with a magnetic stirrer. The stirring time is necessary to allow the water in the atmosphere and the metal alkoxide to undergo hydrolysis and polycondensation reactions. Any sufficient amount of time is fine, for example, 4 hours at 25°C and 90% RH humidity (Relative It can be performed under conditions of humidity (relative humidity). Also, humidity control, In an atmosphere where temperature control is not available, for example, in the atmospheric environment inside a fume hood You may then stir the mixture. In such cases, it is preferable to increase the stirring time. For example, you could leave it at room temperature for 12 hours or more.
[0225] By reacting water vapor in the atmosphere with metal alkoxides, it is possible to achieve a higher rate than when adding liquid water. It also allows the sol-gel reaction to proceed slowly. Furthermore, metal alkoxides and water can be reacted at room temperature. By reacting, for example, heating at a temperature exceeding the boiling point of the solvent alcohol is possible. The sol-gel reaction can proceed slowly. This allows for the formation of a high-quality coating layer with uniform thickness.
[0226] For example, when adding aluminum as metal M2, the relative number of atoms of metal M2 For example, with respect to the sum of metal M1 and metal M2, it is preferable that the value is between 0.0005 and 0.02. A value of 0.001 or more and 0.015 or less is more preferable, and a value of 0.001 or more and 0.009 or less is even more preferable. It seems so. When nickel is added as metal M2, the relative value of the number of atoms of metal M2 is, for example, The sum of metal M1 and metal M2 is preferably 0.0005 or more and 0.02 or less, and 0.0 A value of 0.01 to 0.015 is more preferable, and a value of 0.001 to 0.009 is even more preferable. .
[0227] <Step S43> Next, in step S43, the precipitate is recovered from the mixed liquid after the above treatment is completed. The resulting residue is dried to obtain mixture 904. Methods for recovering the precipitate include filtration, centrifugation, Evaporation to dryness can be applied. The precipitate is the same as the solvent in which the metal alkoxide was dissolved. It can be cleaned with alcohol. The drying process is, for example, at 80°C for 1 to 4 hours. It can be dried under vacuum or by forced air. Note that when using evaporation to dryness, this step... In step P, separation of the solvent and precipitate is not required, for example, in the next step (step In the calcination process of S44), the precipitate should be recovered.
[0228] <Step S44> Next, in step S44, the resulting mixture 904 is calcined.
[0229] The baking time should preferably be between 1 hour and 50 hours within the specified temperature range. Ideally, the baking time should be between 2 and 20 hours. If the baking time is too short, the surface layer will be formed. Compounds containing the metal M2 may have low crystallinity. Alternatively, the diffusion of metal M2 may be impaired. In some cases, it may be sufficient. Or, organic matter may remain on the surface. However, the firing time If the length is too long, the diffusion of metal M2 will proceed too much, potentially leading to low concentrations in the surface layer and near grain boundaries. This is a problem. Furthermore, productivity decreases.
[0230] The specified temperature is preferably between 500°C and 1200°C, and between 700°C and 920°C. More preferably, 800°C to 900°C is preferred. If the specified temperature is too low, the table will not display The crystallinity of compounds containing metal M2 formed in the layer may be low. Alternatively, metal M In some cases, the diffusion of step 2 may be insufficient, or organic matter may remain on the surface.
[0231] Furthermore, firing is preferably carried out in an oxygen-containing atmosphere. When the oxygen partial pressure is low, the firing temperature If the level is not lowered further, there is a risk of Co being reduced.
[0232] In this embodiment, the specified temperature is set to 850°C and maintained for 2 hours, and the temperature rise is 200 The temperature is set to °C / h, and the oxygen flow rate is 10 L / min.
[0233] For cooling after firing, a longer cooling time is preferable as it helps stabilize the crystal structure. If so, it is preferable that the cooling time from the specified temperature to room temperature be between 10 hours and 50 hours. Here, the firing temperature in step S44 is higher than the firing temperature in step S33. A low value is preferable.
[0234] <Step S45> Next, in step S45, the cooled particles are collected, and the positive electrode active material 1 according to one aspect of the present invention is collected. 00 can be produced. At this time, the recovered particles are further sieved. It is preferable.
[0235] This embodiment can be implemented in appropriate combination with other embodiments.
[0236] (Embodiment 3) In this embodiment, it is used in a secondary battery having a positive electrode active material as described in the previous embodiment. Examples of materials that can be used for this purpose will be explained.
[0237] <Example of a secondary battery configuration 1> The following explanation uses a secondary battery, in which the positive electrode, negative electrode, and electrolyte are enclosed in an outer casing, as an example. do.
[0238] [Positive electrode] The positive electrode comprises a positive electrode active material layer and a positive electrode current collector.
[0239] <Cathode active material layer> The positive electrode active material layer has at least positive electrode active material. In addition, it may include other substances such as a coating on the surface of the active material, a conductive additive, or a binder.
[0240] As the positive electrode active material, the positive electrode active material 100 described in the previous embodiment can be used. By using the positive electrode active material 100 described in the previous embodiment, high capacity and cycle characteristics can be achieved. It can be used as a secondary battery with excellent performance.
[0241] As a conductive additive, carbon materials, metal materials, or conductive ceramic materials can be used. This is possible. In addition, fibrous materials may be used as conductive additives. The content of the conductive additive is preferably 1 wt% to 10 wt%, and preferably 1 wt% to 5 wt%. The bottom one is preferable.
[0242] Conductive additives can be used to form an electrical conduction network within the active material layer. The auxiliary agent can maintain the electrical conduction pathways between the positive electrode active materials. By adding a conductive additive, it is possible to realize an active material layer with high electrical conductivity. ru.
[0243] Examples of conductive additives include natural graphite, artificial graphite such as mesocarbon microbeads, and carbon. Fibers can be used. For example, mesophase pitch carbon fibers can be used. Carbon fibers such as fiber and isotropic pitch carbon fibers can be used. Carbon nanofibers and carbon nanotubes can be used. Notubes can be fabricated, for example, by vapor phase growth. Also, as a conductive additive, For example, carbon black (acetylene black (AB), etc.), graphite particles. Carbon materials such as ions, graphene, and fullerenes can be used. Also, for example, copper, Metal powders and fibers such as nickel, aluminum, silver, and gold, and conductive ceramic materials, etc. You can use it.
[0244] Furthermore, graphene compounds may be used as conductive additives.
[0245] Graphene compounds possess excellent electrical properties, including high conductivity, and high flexibility. It may possess excellent physical properties such as high mechanical strength. The compound has a planar shape. The graphene compound enables surface contact with low contact resistance. Furthermore, even thin materials can have very high conductivity, allowing for efficient use within the active material layer in small quantities. A conductive path can be formed. Therefore, graphene compounds are used as conductive additives. This is preferable because it increases the contact area between the active material and the conductive additive. By using a plate-drying device, the entire surface of the active material is covered with graphene, which is a conductive additive. It is preferable to form the compound as a coating. Furthermore, it may be possible to reduce electrical resistance. Therefore, it is preferable. Here, as graphene compounds, for example, graphene, multigraphene , or it is particularly preferable to use RGO. Here, RGO is, for example, graphene oxide ( This refers to compounds obtained by reducing graphene oxide (GO).
[0246] When using active materials with small particle sizes, for example, active materials with particle sizes of 1 μm or less, the specific surface area of the active material The coefficient of conductivity is large, requiring more conductive paths to connect the active materials. Therefore, the amount of conductive additive is large. This tends to happen, and relatively, the amount of active material carried decreases. If the amount decreases, the capacity of the secondary battery will decrease. In such cases, a conductive additive is used. When graphene compounds are used, even small amounts of graphene compounds efficiently form conductive paths. This is particularly preferable because it does not require reducing the amount of active material supported.
[0247] In the following example, a graphene compound is used as a conductive additive in the active material layer 200. An example of a cross-sectional configuration of the joint will be explained.
[0248] Figure 11A shows a longitudinal cross-sectional view of the active material layer 200. The active material layer 200 consists of granular positive electrode active material. It contains 100, a graphene compound 201 as a conductive additive, and a binder (not shown). Hmm. Here, as graphene compound 201, for example, graphene or multigraphene It is fine to use it. Here, it is preferable that the graphene compound 201 has a sheet-like shape. Furthermore, graphene compound 201 is a multigraphene, or (and) multiple graphenes. The graphene may be partially overlapping and form a sheet.
[0249] In the longitudinal section of the active material layer 200, as shown in Figure 11B, the interior of the active material layer 200 In Figure 11B, the graphene compound 201 is dispersed in a roughly uniform sheet-like manner. Although the rafen compound 201 is schematically represented by a thick line, it is actually a single or multilayer carbon molecule. It is a thin film having a thickness of [a certain thickness]. Multiple graphene compounds 201 are multiple granular positive electrode active materials. It partially covers 100, or adheres to the surface of multiple granular positive electrode active material 100. Because they are formed in a uniform manner, they are in surface contact with each other.
[0250] Here, multiple graphene compounds bond together to form a network of graphene compounds. Forming a material sheet (hereinafter referred to as graphene compound net or graphene net) This is possible. When the active material is covered with a graphene net, the graphene net interacts with the active material. It can also function as a binder to combine them. Therefore, the amount of binder can be reduced. Because it is possible or not to use the active material in relation to the electrode volume and electrode weight The ratio can be improved. In other words, the capacity of the secondary battery can be increased.
[0251] Here, graphene oxide is used as graphene compound 201 and mixed with the active material to produce the active material It is preferable to form a layer that will become the 200th layer and then reduce it. Formation of graphene compound 201 Furthermore, by using graphene oxide, which has extremely high dispersibility in polar solvents, graphene Compound 201 can be dispersed approximately uniformly within the active material layer 200. The solvent is evaporated and removed from the dispersion medium containing dispersed graphene oxide, and the graphene oxide is returned. Therefore, the graphene compound 201 remaining in the active material layer 200 partially overlaps, By being dispersed to the extent that they are in surface contact with each other, a three-dimensional conductive path can be formed. Furthermore, the reduction of graphene oxide may be carried out, for example, by heat treatment, or by using a reducing agent. You may go.
[0252] Therefore, unlike granular conductive additives such as acetylene black that make point contact with the active material, the graph Since compound 201 enables surface contact with low contact resistance, it is not a typical conductive additive. This method improves the electrical conductivity between granular positive electrode active material 100 and graphene compound 201 using a smaller amount. This can be done. Therefore, the ratio of positive electrode active material 100 in the active material layer 200 can be increased. This allows for an increase in the discharge capacity of the secondary battery.
[0253] Furthermore, by using a spray drying device beforehand, the entire surface of the active material is covered with a conductive additive. A graphene compound is formed as a coating, and the spaces between the active materials are further separated by the graphene compound. It is also possible to form conductive paths.
[0254] Examples of binders include styrene-butadiene rubber (SBR) and styrene-isopropyl alcohol. Lenyl-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene- It is preferable to use a rubber material such as a propylene-diene copolymer as a binder. Therefore, fluororubber can be used.
[0255] Furthermore, it is preferable to use a water-soluble polymer as the binder. As molecules, for example, polysaccharides can be used. As for polysaccharides, carboxymethyl Cholecellulose (CMC), methylcellulose, ethylcellulose, hydroxypropyl Cellulose derivatives such as cellulose, diacetylcellulose, and regenerated cellulose, and starch These can be used. In addition, these water-soluble polymers can be used in combination with the aforementioned rubber material. It is even preferable if used.
[0256] Alternatively, the binder could be polystyrene, methyl polyacrylate, or polymethacrylic acid. Methyl (polymethyl methacrylate, PMMA), sodium polyacrylate, polyvinyl Polyalcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, Polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene Polyethylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer It is preferable to use materials such as polyvinyl acetate and nitrocellulose.
[0257] You may use a combination of several of the binders mentioned above.
[0258] For example, a material with particularly excellent viscosity-modifying properties may be used in combination with other materials. For example, rubber materials have excellent adhesive and elastic properties, but when mixed with a solvent, it is difficult to adjust their viscosity. In such cases, for example, mixing with a material that has particularly excellent viscosity-modifying effects may be necessary. This is preferable. As a material with particularly excellent viscosity adjustment effect, for example, a water-soluble polymer can be used. Good. Also, as water-soluble polymers that are particularly excellent in viscosity adjustment, the aforementioned polysaccharides, for example, Boxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydrox Cellulose inducers such as cypropylcellulose, diacetylcellulose, and regenerated cellulose Conductors and starch can be used.
[0259] Furthermore, cellulose derivatives such as carboxymethylcellulose are, for example, carboxymethyl Solubility increases when cellulose is converted into salts such as sodium salts or ammonium salts. This makes it easier for the viscosity modifier to exert its effect. The increased solubility makes it easier for the electrode slurry to When preparing the Lee, it is also possible to improve the dispersibility of the active material and other components. In this case, the cellulose and cellulose derivatives used as electrode binders are: These salts shall also be included.
[0260] Fluorine-based resins have advantages such as excellent mechanical strength, high chemical resistance, and high heat resistance. PVDF, a type of fluoropolymer resin, possesses extremely superior properties among fluoropolymer resins. It possesses mechanical strength, excellent processability, and high heat resistance.
[0261] On the other hand, with PVDF, when the slurry produced during the coating of the active material layer becomes alkaline... It may gel, or it may become insoluble. This can sometimes lead to a decrease in the adhesion between the current collector and the active material layer. Positive electrode of one aspect of the present invention By using an active material, the pH of the slurry can be lowered, suppressing gelation and insolubilization. It is a good match.
[0262] <Positive electrode current collector> As the positive electrode current collector, metals such as stainless steel, gold, platinum, aluminum, and titanium, and Highly conductive materials such as these alloys can be used. Also, materials used for the positive electrode current collector It is preferable that the material does not dissolve at the positive electrode potential. Also, silicon, titanium, neodymium, and Aluminum alloys to which elements that improve heat resistance, such as candium and molybdenum, have been added. It can be used. Furthermore, it can be formed with a metallic element that reacts with silicon to form a silicide. It may also be the case that, as a metallic element that reacts with silicon to form a silicide, zirconium, Titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten Examples include cellulose, cobalt, and nickel. Current collectors come in foil, plate (sheet), mesh, and perforated forms. Shapes such as metal-like or expanded metal-like can be used as appropriate. The current collector has a thickness It is best to use particles that are between 5 μm and 30 μm in size.
[0263] [Method for manufacturing the positive electrode] As an example of a method for producing a positive electrode having a positive electrode active material according to one aspect of the present invention, a slurry is prepared. The slurry can be used to fabricate electrodes. Here is an example of how to make Lee.
[0264] Here, the solvent used to prepare the slurry is preferably a polar solvent. For example, water methanol, ethanol, acetone, tetrahydrofuran (THF), dimethylform Amides (DMF), N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMS) One or more of the following solutions (O) can be used.
[0265] In one embodiment of the present invention, when the positive electrode active material has a first particle group and a second particle group, the first particle The first group of particles and the second group of particles are mixed in the desired ratio. The mixing ratio is first group of particles:second group of particles. When the group ratio is 1:w (weight ratio), w is preferably 0.01 or more and 0.6 or less, more preferably The ratio is 0.03 or more and 0.6 or less, more preferably 0.04 or more and 0.5 or less, even more preferably The value is between 0.09 and 0.3.
[0266] A positive electrode active material according to one aspect of the present invention has a particle size ratio corresponding to the mixing ratio of a first particle group and a second particle group. There may be a distribution. Also, depending on the proportion of each particle group, each particle group The intensity or area of the corresponding maximum peak has a magnitude value that corresponds to the ratio of that proportion. There are cases where this is the case. Also, a single group of particles may have one maximum peak, or it may have two or more. In cases where there are two or more peaks, it may be sufficient to use the sum of the areas under the peaks of the peaks.
[0267] A positive electrode active material comprising a mixture of a first particle group and a second particle group, a conductive additive, and a binder. Mix the solvent and to prepare mixture J. The mixing may be carried out under normal pressure or under reduced pressure. For example, a kneader can be used in the mixing process.
[0268] Next, measure the viscosity of mixture J. Then, adjust the viscosity by adding solvent as needed. The above steps are performed to obtain a slurry for coating the active material layer.
[0269] Here, for example, the higher the viscosity of mixture J, the more active material, binder, Furthermore, the dispersibility of conductive additives is excellent (they mix well with each other). Therefore, for example, A higher viscosity is preferable for mixture J. On the other hand, if the viscosity of mixture J is too high, For example, the electrode coating speed may be low, which is undesirable from a productivity standpoint. .
[0270] Next, we will explain a method for creating an active material layer on a current collector using the prepared slurry. ru.
[0271] First, apply the slurry to the current collector. Before applying the slurry, apply the slurry to the current collector. Surface treatment may be performed. Examples of surface treatments include corona discharge treatment, plasma treatment, Examples include undercoating. Here, undercoating refers to applying slurry to the current collector. Before coating, the purpose is to reduce the interfacial resistance between the active material layer and the current collector, and the interaction between the active material layer and the current collector. This refers to a film formed on a current collector to improve adhesion. Note that the term "undercoat" does not necessarily mean "undercoat." It does not need to be in the form of a membrane; it may be formed in the form of islands. Also, the undercoat is the active material and It is acceptable to express capacity in this way. For the undercoat, for example, a carbon material can be used. This can be done. Examples of carbon materials include graphite, acetylene black, and Ketjenblack. Carbon black, carbon nanotubes, etc. (registered trademark) can be used.
[0272] Slurry application can be done using slot die methods, gravure methods, blade methods, and combinations thereof. A combination of methods can be used. Furthermore, a continuous coating machine may be used for application.
[0273] Next, the active material layer can be formed by evaporating the solvent in the slurry.
[0274] The solvent evaporation step of the slurry is performed at a temperature of 50°C to 200°C, preferably 60°C to 90°C. The following temperature range is recommended. Evaporation can be carried out, for example, under normal atmospheric pressure in an air atmosphere, or under reduced pressure. It can also be done below. Evaporation time can sometimes be shortened by performing the process under reduced pressure. In some cases, this can lower the evaporation temperature.
[0275] The evaporation process can be carried out using a hot plate, drying oven, etc.
[0276] The active material layer may be formed on both sides of the current collector, or on only one side. Alternatively, it may have regions where active material layers are formed on both sides in part.
[0277] After evaporating the solvent from the active material layer, compression is performed using methods such as roll pressing or flat plate pressing. Pressing is preferable.
[0278] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer also contains a conductive additive. It may have a binder.
[0279] <Negative electrode active material> For example, alloy materials or carbon-based materials can be used as the negative electrode active material.
[0280] As a negative electrode active material, the charge-discharge reaction is carried out through alloying and dealloying reactions with lithium. Any possible element can be used. For example, silicon, tin, gallium, aluminum, Germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. Materials containing at least one of these elements can be used. Such elements have a capacity compared to carbon. Larger, and especially silicon, has a high theoretical capacity of 4200 mAh / g. Therefore, the negative electrode active material Silicon is preferred. Compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag 3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, Examples include InSb and SbSn. Here, charging and discharging occur through alloying and dealloying reactions with lithium. In some cases, elements capable of carrying out reactions, and compounds containing such elements, are referred to as alloying materials. be.
[0281] In this specification, SiO refers to silicon monoxide, for example. Alternatively, SiO refers to Si O x It can also be expressed as follows. Here, it is preferable that x has one neighboring value. For example, x is A value of 0.2 to 1.5 is preferred, and a value of 0.3 to 1.2 is more preferred.
[0282] Carbon-based materials include graphite, easily graphitizable carbon (soft carbon), and poorly graphitizable carbon (hard carbon). Using carbon fiber, carbon nanotubes, graphene, carbon black, etc. stomach.
[0283] Examples of graphite include artificial graphite and natural graphite. For example, meso Examples include carbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, spheroidal graphite, which has a spherical shape, can be used as artificial graphite. For example, MCMB may have a spherical shape, which is preferable. Also, the surface of MCMB Reducing the product is relatively easy and sometimes preferable. Examples of natural graphite include Examples include flaky graphite and spheroidized natural graphite.
[0284] Graphite is formed when lithium ions are inserted into it (during the formation of lithium-graphite intercalation compounds). ) exhibits a potential as low as lithium metal (0.05V to 0.3V vs. Li / Li + This allows lithium-ion rechargeable batteries to exhibit a high operating voltage. Furthermore, graphite has a relatively high capacity per unit volume, relatively small volume expansion, and is inexpensive. It is preferable because it has advantages such as higher safety compared to lithium metal.
[0285] Furthermore, titanium dioxide (TiO2) and lithium titanium oxide (Li4) are used as negative electrode active materials. Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5) ), use oxides such as tungsten oxide (WO2) and molybdenum oxide (MoO2). It is possible.
[0286] Furthermore, as the negative electrode active material, a Li3N type structure, which is a lithium and transition metal binitride, is also used. TsuLi 3-x M x N (M = Co, Ni, Cu) can be used. For example, Li 2. 6Co 0.4 The N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm²). 3 )of This is preferable.
[0287] When using a lithium-transition metal binitride, lithium ions are included in the negative electrode active material. In combination with materials such as V2O5 and Cr3O8 that do not contain lithium ions as the positive electrode active material. It is preferable that this be done. Furthermore, when using a material containing lithium ions as the positive electrode active material, Also, by pre-desorbing the lithium ions contained in the positive electrode active material, the negative electrode active material and Therefore, a lithium-transition metal composite can be used.
[0288] Furthermore, materials that undergo a conversion reaction can also be used as the negative electrode active material. For example For example, lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO). Transition metal oxides that do not form alloys with mu may be used as the negative electrode active material. Conversion reaction Materials that produce this include Fe2O3, CuO, Cu2O, RuO2, and Cr2O3. Oxides such as CoS 0.89 , sulfides such as NiS and CuS, Zn3N2, Cu3N, Ge Nitrides such as 3N4, phosphides such as NiP2, FeP2, CoP3, FeF3, BiF3, etc. This also occurs with fluorides.
[0289] The conductive additives and binders that the negative electrode active material layer may have are, for example, the positive electrode active material layer Materials similar to those used for conductive additives and binders can be used.
[0290] <Negative electrode current collector> The negative electrode current collector can be made of the same material as the positive electrode current collector. It is preferable to use a material that does not alloy with carrier ions such as lithium.
[0291] [Electrolyte] An electrolyte solution contains a solvent and an electrolyte. A non-protic organic solvent is preferred as the solvent for the electrolyte solution. For example, ethylene carbonate (EC), propylene carbonate (PC), br Tylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyro Lactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate Tyl, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-Dioxane, 1,4-Dioxane, Dimethoxyethane (DME), Dimethyl Sulfane Hoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetra One of the following, or two or more of these: trahydrofuran, sulfolane, sultone, etc. It can be used in combinations and ratios.
[0292] Furthermore, as the solvent for the electrolyte, an ionic liquid (a room-temperature molten salt) that is flame-retardant and non-volatile is used. By using one or more of these devices, the internal temperature of the secondary battery may rise due to internal short circuits or overcharging. However, this can prevent secondary batteries from rupturing or catching fire. Ionic liquids are composed of cations and anions. It consists of and contains organic cations and anions. As organic cations used in the electrolyte, four quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations Aliphatic onium cations such as imidazolium cations and pyridinium cations, etc. Aromatic cations are an example. In addition, monovalent amides are used as anions in the electrolyte. Anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkyl Anions of tetrafluoroborate, perfluoroalkyl volate Toanions, hexafluorophosphate anions, or perfluoroalkyl phosphates Examples include ether anions.
[0293] Furthermore, examples of electrolytes to be dissolved in the above solvent include LiPF6, LiClO4, and L. iAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO 4. Li2B 10 Cl 10 Li2B 12 Cl 12 LiCF3SO3, LiC4F9S O3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2 LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, etc. Using one type of thium salt, or two or more of these in any combination and ratio. It is possible.
[0294] The electrolyte used in secondary batteries contains particulate matter and elements other than the constituent elements of the electrolyte (hereinafter simply referred to as " It is preferable to use a highly purified electrolyte with a low content of impurities (also called "foulings"). Specifically, the weight ratio of impurities to the electrolyte is 1% or less, preferably 0.1% or less. Preferably, the amount is 0.01% or less.
[0295] Furthermore, the electrolyte contains vinylene carbonate, propanesultone (PS), and tert-butyl. Benzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxa) LiBOB (Lithium-Borate), as well as dinitriles such as succinonitrile and adiponitrile. Additives such as solvent compounds may be added. The concentration of the added material should be, for example, relative to the total solvent. The concentration should be between 0.1 wt% and 5 wt%.
[0296] Alternatively, a polymer gel electrolyte, obtained by swelling a polymer with an electrolyte solution, may be used.
[0297] Using polymer gel electrolytes enhances safety against leakage and other issues. The pond can be made thinner and lighter.
[0298] Examples of polymers that can be gelled include silicone gel, acrylic gel, and acrylonitrile gel. Polyethylene oxide gel, polypropylene oxide gel, fluorine polymer Gels and the like can be used.
[0299] Examples of polymers include polyalkylene oxides such as polyethylene oxide (PEO). Polymers having a side structure, PVDF, polyacrylonitrile, etc., and those Copolymers containing the above can be used. For example, PVDF and hexafluoropropylene ( PVDF-HFP, a copolymer of HFP, can be used. The rimer may have a porous structure.
[0300] Furthermore, instead of an electrolyte, a solid electrolyte containing inorganic materials such as sulfide-based or oxide-based materials may be used. Solid electrolytes containing polymer materials such as PEO (polyethylene oxide) can be used. It is possible. When using a solid electrolyte, the installation of separators and spacers becomes unnecessary. Also, Because the entire battery can be made solid, the risk of leakage is eliminated, dramatically improving safety.
[0301] [Separator] Furthermore, it is preferable that the secondary battery has a separator. Examples of separators include: Paper, nonwoven fabric, glass fiber, ceramics, or nylon (polyamide), vinylon (poly (vinyl alcohol-based fibers), polyester, acrylic, polyolefin, polyurethane A separator made of synthetic fibers or the like can be used. It is preferable to process it into a shape and arrange it so as to enclose either the positive or negative electrode.
[0302] The separator may have a multilayer structure. For example, an organic material such as polypropylene or polyethylene. The material film contains ceramic-based materials, fluorine-based materials, polyamide-based materials, or a combination thereof. Mixtures and other materials can be coated onto it. Examples of ceramic materials include aluminum oxide. Aluminum particles, silicon oxide particles, etc. can be used. Examples of fluorine-based materials include PVDF, polytetrafluoroethylene, etc. can be used. Polyamide materials and For example, nylon, aramid (meta-aramid, para-aramid), etc. can be used. It is possible.
[0303] Coating with ceramic materials improves oxidation resistance, thus preventing separation during high-voltage charging and discharging. This can suppress the degradation of the data and improve the reliability of secondary batteries. Furthermore, fluorine-based materials... Coating the electrode makes it easier for the separator and electrode to adhere to each other, which can improve the output characteristics. Coating with polyamide materials, especially aramid, improves heat resistance, thus improving the heat resistance of secondary batteries. Safety can be improved.
[0304] For example, a mixture of aluminum oxide and aramid material is applied to both sides of a polypropylene film. It may also be done by applying aluminum oxide to the surface of the polypropylene film that is in contact with the positive electrode. A mixed material of um and aramid may be coated, and a fluorine-based material may be coated on the surface in contact with the negative electrode. .
[0305] Using a multilayer separator ensures the safety of secondary batteries even with a thin overall separator. Because this can be maintained, the capacity per unit volume of the secondary battery can be increased.
[0306] [Exterior] For the casing of a secondary battery, metal materials such as aluminum or resin materials are used. It is possible to have it. Also, a film-like outer covering can be used. For example, polyethylene, polypropylene, polycarbonate, ionomer, polyamide On a film made of materials such as aluminum, stainless steel, copper, nickel, etc., which have excellent flexibility A thin metal film is provided, and on the thin metal film, a polyamide resin, polyester resin, etc. are used as the outer surface of the exterior body. A three-layer film with an insulating synthetic resin film, such as a tellate resin, can be used.
[0307] <Example of a secondary battery configuration 2> Below is an example of a secondary battery configuration, specifically a secondary battery configuration using a solid electrolyte layer. explain.
[0308] As shown in Figure 12A, a secondary battery 400 according to one aspect of the present invention comprises a positive electrode 410 and a solid electrolyte. It has a layer 420 and a negative electrode 430.
[0309] The positive electrode 410 has a positive electrode current collector 413 and a positive electrode active material layer 414. 4 has a positive electrode active material 411 and a solid electrolyte 421. The positive electrode active material layer 414 is a guide It may contain an electrolytic agent and a binder.
[0310] The solid electrolyte layer 420 has a solid electrolyte 421. The solid electrolyte layer 420 has a positive electrode 410. It is located between the positive electrode active material 411 and the negative electrode 430, and does not contain either the positive electrode active material 411 or the negative electrode active material 431. It is a difficult area.
[0311] The negative electrode 430 has a negative electrode current collector 433 and a negative electrode active material layer 434. 4 has a negative electrode active material 431 and a solid electrolyte 421. The negative electrode active material layer 434 is a guide It may contain an electrolytic agent and a binder. Alternatively, as shown in Figure 12B, the negative electrode 430 can be made without the solid electrolyte 421. Using metallic lithium in the negative electrode 430 improves the energy density of the secondary battery 400. This is desirable.
[0312] Also, as shown in Figure 13A, the set consists of a positive electrode 410, a solid electrolyte layer 420, and a negative electrode 430. A secondary battery may be formed by stacking multiple positive electrodes 410 and a solid electrolyte layer 420. By stacking the negative electrode 430, the voltage of the secondary battery can be increased. Figure 13A shows When a combination of positive electrode 410, solid electrolyte layer 420, and negative electrode 430 is stacked in four layers, the approximate value is This is a schematic diagram.
[0313] Furthermore, a secondary battery according to one embodiment of the present invention may be a thin-film all-solid-state battery. Ponds are constructed using vapor phase methods (vacuum deposition, pulsed laser deposition, aerosol deposition, sputtering). Positive electrodes, solid electrolytes, negative electrodes, wiring electrodes, etc., can be fabricated by forming films using this method. For example, Figure 13B shows an example of a thin-film all-solid-state battery 450. As shown in Figure 13B, the substrate 44 After forming wiring electrodes 441 and 442 on 0, a positive electrode 41 is placed on wiring electrode 441. A 0 is formed, and a solid electrolyte layer 420 is formed on the positive electrode 410, and the solid electrolyte layer 420 and the A thin-film all-solid-state battery 450 can be fabricated by forming a negative electrode 430 on the wire electrode 442. The substrate 440 can be a ceramic substrate, a glass substrate, a plastic substrate, a metal substrate, etc. You can use these.
[0314] The solid electrolyte 421 in the solid electrolyte layer 420 may be, for example, a sulfide-based solid electrolyte. Oxide-based solid electrolytes, halide-based solid electrolytes, etc., can be used.
[0315] Sulfide-based solid electrolytes include thiosilicon-based (Li 10 GeP2S 12 Li 3.25 G e 0.25 P 0.75 S4, etc.), sulfide glass (70Li2S・30P2S5, 30Li 2S·26B2S3·44LiI, 63Li2S·38SiS2·1Li3PO4, 57 Li2S・38SiS2・5Li4SiO4, 50Li2S・50GeS2, etc.), sulfides Crystallized glass (Li7P3S 11 Li 3.25 P 0.95 Contains sulfides (S4, etc.). Solid electrolytes have materials with high conductivity, can be synthesized at low temperatures, and are relatively soft. Because it is soft, it has advantages such as the conductivity path being easily maintained even after charging and discharging.
[0316] Oxide-based solid electrolytes include materials having a perovskite-type crystal structure (La 2 / 3-x L i 3x Materials having a NASICON-type crystal structure (Li 1-X Al X Ti2 -X (PO4)3, etc.), materials having a garnet-type crystal structure (Li7La3Zr2O 12 , etc.), materials having a LISICON-type crystal structure (Li 14 ZnGe4O 16 , etc.), LLZ O (Li7La3Zr2O 12 ), oxide glasses (Li3PO4-Li4SiO4, 50 Li4SiO4·50Li3BO3, etc.), oxide crystallized glasses (Li 1.07 Al 0.6 9Ti 1.46 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, etc.) are include d. Oxide-based solid electrolytes have the advantage of being stable in the atmosphere.
[0317] Halide-based solid electrolytes include LiAlCl4, Li3InBr6, LiF, LiC l, LiBr, LiI, and the like. Further, composite materials obtained by filling these halide-based solid electrolytes into pores of porous al umina or porous silica can also be used as solid electrolytes.
[0318] Alternatively, different solid electrolytes may be mixed and used.
[0319] Among these, Li having a NASICON-type crystal structure 1+x Al x Ti 2-x (PO4)3 (0 < x < 1) (hereinafter referred to as LATP) contains aluminum and titanium, which are elements that may be contained in the positive electrode active material 100 of one embodiment of the present invention, so a synergistic effect on improving cycle characteristics can be expected, which is preferable. In addition, improvement in productivity through process reduction can also be expected. In the present specification and the like, the NASICON-type crystal structure refers to M2(XO4)3 (M: transition metal, X: S It is a compound represented by (P, As, Mo, W, etc.), with MO6 octahedrons and XO4 tetrahedrons at its vertices. This refers to a structure that shares elements and is arranged in a three-dimensional manner.
[0320] [Shape of the outer casing and secondary battery] The casing of the secondary battery 400 according to one aspect of the present invention can be made of various materials and shapes. While this is possible, it is preferable that the positive electrode, solid electrolyte layer, and negative electrode have a function to pressurize them. .
[0321] For example, Figure 14 shows an example of a cell used to evaluate the materials of an all-solid-state battery.
[0322] Figure 14A is a schematic cross-sectional view of the evaluation cell, which consists of a lower member 761 and an upper member 7 62 and fixing screws and wing nuts 764 that secure them, and a retaining screw 763 that rotates By rotating it, the electrode plate 753 is pressed and the evaluation material is fixed in place. Made of stainless steel. An insulator 766 is provided between the constructed lower member 761 and the upper member 762. Also, between the upper member 762 and the retaining screw 763, there is an O-ring 765 for sealing. A system is in place.
[0323] The evaluation material is placed on an electrode plate 751, surrounded by an insulating tube 752, and subjected to electric current from above. The material is being pressed by polar plate 753. This is a magnified perspective view of the area surrounding this evaluation material. This is shown in Figure 14B.
[0324] As an example of the evaluation material, we used a stacked configuration consisting of a positive electrode 750a, a solid electrolyte layer 750b, and a negative electrode 750c. This is shown, and a cross-sectional view is shown in Figure 14C. Note that the same applies to Figures 14A, 14B, and 14C. The same symbol is used in the same place.
[0325] The electrode plate 751 and lower member 761, which are electrically connected to the positive electrode 750a, are the positive electrode It can be said that this corresponds to a terminal. Electrode plate 7 is electrically connected to the negative electrode 750c. 53 and the upper member 762 can be said to correspond to the negative electrode terminal. Electrode plate 7 Electrical resistance and other properties are measured while applying pressure to the evaluation material via electrode plate 753 and electrode plate 51. It is possible.
[0326] Furthermore, the outer casing of the secondary battery according to one embodiment of the present invention uses a package with excellent airtightness. Preferably, ceramic packages or resin packages can be used. Furthermore, when sealing the outer casing, it is necessary to block out outside air and create a sealed atmosphere, for example, a glove box. It is preferable to perform this within the premises.
[0327] Figure 15A shows a secondary battery according to one embodiment of the present invention, having a different exterior and shape from that of Figure 14. A visual view is shown. The secondary battery in Figure 15A has external electrodes 771 and 772 and multiple packages. It is sealed with an exterior body containing components.
[0328] Figure 15B shows an example of a cross-section cut along the dashed line in Figure 15A. Positive electrode 750a, solid-state battery The laminate having a decomposition layer 750b and a negative electrode 750c has an electrode layer 773a provided on a flat plate. A package member 770a, a frame-shaped package member 770b, and an electrode layer 773b on a flat plate. The package component 770c, which is provided with a packing mechanism, is enclosed and sealed by a packing mechanism. The cage members 770a, 770b, and 770c are made of insulating material, such as resin or ceramic. You can use it.
[0329] The external electrode 771 is electrically connected to the positive electrode 750a via the electrode layer 773a, and the positive electrode end It functions as a child. In addition, the external electrode 772 is electrically connected to the negative electrode 750c via the electrode layer 773b. It is electrically connected and functions as a negative terminal.
[0330] This embodiment can be used in appropriate combination with other embodiments.
[0331] (Embodiment 4) In this embodiment, the form of a secondary battery having the positive electrode active material 100 described in the previous embodiment Let me explain an example of the shape. The material used in the secondary battery described in this embodiment is the same as in the previous embodiment. The description of the form can be taken into consideration.
[0332] [Coin-type rechargeable battery] First, let's explain an example of a coin-type rechargeable battery. Figure 16A shows a coin-type (single-layer flattened) battery. Figure 16B is an external view of the secondary battery, and Figure 16B is a cross-sectional view thereof.
[0333] The coin-type rechargeable battery 300 consists of a positive electrode casing 301 which also serves as the positive electrode terminal and a negative electrode casing which also serves as the negative electrode terminal. The can 302 is insulated and sealed with a gasket 303 made of polypropylene or the like. The positive electrode 304 consists of a positive electrode current collector 305 and a positive electrode active material layer 30 provided in contact with it. It is formed by 6. The negative electrode 307 is provided with the negative electrode current collector 308 and is set to be in contact with it. It is formed by the kerned negative electrode active material layer 309.
[0334] Furthermore, the positive electrode 304 and negative electrode 307 used in the coin-type secondary battery 300 are each active The material layer only needs to be formed on one side.
[0335] The positive electrode can 301 and negative electrode can 302 contain nickel and aluminum, which are corrosion-resistant to the electrolyte. Metals such as titanium, or alloys of these or alloys of these with other metals (for example, stainless steel) Steel, etc. can be used. In addition, nickel or aluminum can be used to prevent corrosion by the electrolyte. It is preferable to coat with aluminum or the like. Positive electrode can 301 is positive electrode 304, and negative electrode can 302 is negative electrode 3 Connect each of them electrically to 07.
[0336] These negative electrode 307, positive electrode 304, and separator 310 are impregnated with the electrolyte, as shown in Figure 16B. As shown, with the positive electrode can 301 at the bottom, the positive electrode 304, separator 310, negative electrode 307, and negative The electrode cans 302 are stacked in this order, and the positive electrode can 301 and the negative electrode can 302 are connected via a gasket 303. The coin-shaped rechargeable battery 300 is manufactured by crimping the parts together.
[0337] By using the positive electrode active material described in the previous embodiment for the positive electrode 304, high capacity cycling is achieved. This allows for the creation of a coin-type secondary battery 300 with excellent performance characteristics.
[0338] Here, we will use Figure 16C to explain the current flow during the charging of a secondary battery. When a secondary battery is considered as a closed circuit, the movement of lithium ions and the flow of current are in the same direction. Yes. In lithium-ion secondary batteries, the anode and cathode are used during charging and discharging. The cathode is swapped, and the oxidation and reduction reactions are reversed, so the reaction potential changes. The electrode with the higher potential is called the positive electrode, and the electrode with the lower reaction potential is called the negative electrode. Therefore, in this specification Therefore, whether charging or discharging, or even when applying a reverse pulse current, Even when an electric current is flowing, the positive electrode is called the "positive electrode" or "+ electrode (plus electrode)," and the negative electrode is called the "negative electrode." We will refer to this as the "negative electrode" or "- electrode (minus electrode)." In relation to oxidation and reduction reactions... If we use the terms anode and cathode, then during charging and discharging, This could be reversed and cause confusion. Therefore, the anode and cathode The term (cathode) will not be used in this specification. When using the terms cathode, specify whether it is during charging or discharging, and indicate the positive electrode ( We will also indicate whether it corresponds to the negative (last) or last (minus) pole.
[0339] The charger is connected to the two terminals shown in Figure 16C, and the secondary battery 300 is charged. As the 300 battery charges, the potential difference between the electrodes increases.
[0340] [Cylindrical rechargeable battery] Next, an example of a cylindrical secondary battery will be explained with reference to Figure 17. Cylindrical secondary battery 60 Figure 17A shows an external view of the 0. Figure 17B schematically shows a cross-section of the cylindrical secondary battery 600. The diagram below shows that, as shown in Figure 17B, the cylindrical secondary battery 600 has a positive electrode cap on its top surface. It has a (battery cover) 601 and battery cans (outer casings) 602 on its sides and bottom. The positive electrode cap and the battery can (outer casing) 602 are separated by a gasket (insulating packing) 610. They've been cut off from each other.
[0341] Inside the hollow cylindrical battery can 602, there is a separator between the strip-shaped positive electrode 604 and the negative electrode 606. A battery element is provided, wound with a 605 in between. Although not shown in the diagram, the battery element is It is wound around the center pin. The battery can 602 is closed at one end and open at the other end. The battery can 602 contains nickel, aluminum, and titanium, which are corrosion-resistant to the electrolyte. Metals such as these, or alloys thereof, or alloys of these with other metals (for example, stainless steel, etc.) It can be used. In addition, nickel, aluminum, etc. can be used to prevent corrosion by the electrolyte. It is preferable to cover the battery can 602. Inside the battery can 602, the positive electrode, the negative electrode and The battery element, around which the separator is wound, is sandwiched between a pair of opposing insulating plates 608 and 609. Furthermore, the inside of the battery can 602, which is equipped with the battery element, contains a non-aqueous electrolyte (not shown). It is injected. The non-aqueous electrolyte can be the same as that used in coin-type rechargeable batteries. ru.
[0342] Since the positive and negative electrodes used in cylindrical storage batteries are wound, active material is formed on both sides of the current collector. It is preferable to do so. The positive electrode 604 is connected to the positive electrode terminal (positive electrode current collector lead) 603, and the negative The negative terminal (negative current collector lead) 607 is connected to pole 606. The positive terminal 603 and the negative Both electrode terminals 607 can be made of metal materials such as aluminum. Positive electrode terminal 6 Terminal 03 is resistance-welded to the safety valve mechanism 612, and the negative terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 612 uses a PTC element (Positive Temperature C It is electrically connected to the positive electrode cap 601 via the efficient)611. The safety valve mechanism 612 activates the positive electrode cap 601 when the internal pressure of the battery rises above a predetermined threshold. This disconnects the electrical connection between the positive electrode 604 and the positive electrode 611. Also, the PTC element 611 is at a certain temperature. This is a thermal resistance element whose resistance increases when the temperature rises, and the increase in resistance limits the amount of current. This prevents abnormal heat generation. The PTC element uses barium titanate (BaTiO3) Semiconductor ceramics and the like can be used.
[0343] Furthermore, as shown in Figure 17C, multiple secondary batteries 600 are connected to conductive plates 613 and 614. Module 615 may be configured by inserting it in between. Multiple secondary batteries 600 are connected in parallel. They may be connected in series, or they may be connected in parallel and then further connected in series. It may be. By configuring a module 615 having multiple secondary batteries 600, It can extract a large amount of electricity.
[0344] Figure 17D is a top view of module 615. To make the diagram clearer, the conductive plate 613 is pointed. As shown by the lines, module 615 electrically powers multiple secondary batteries 600 as shown in Figure 17D. It may have a conductor 616 connected to it. A conductive plate may be superimposed on the conductor 616. This is possible. Furthermore, a temperature control device 617 may be provided between multiple secondary batteries 600. When the secondary battery 600 overheats, the temperature control device 617 cools it down, and the secondary battery 600 When it gets too cold, it can be heated by the temperature control device 617. The performance of the 615 becomes less affected by the ambient temperature. The heat transfer medium of the temperature control device 617 is It is preferable that the material has insulating and non-flammable properties.
[0345] By using the positive electrode active material described in the previous embodiment for the positive electrode 604, high capacity cycling is achieved. A cylindrical secondary battery 600 with excellent performance characteristics can be produced.
[0346] [Example of a secondary battery structure] Another example of a secondary battery structure will be explained using Figures 18 to 22.
[0347] Figures 18A and 18B show the external view of the secondary battery. The secondary battery 913 is part of the circuit. It is connected to antennas 914 and 915 via circuit board 900. The next battery 913 has label 910 attached to it. Furthermore, as shown in Figure 18B, Battery 913 is connected to terminals 951 and 952.
[0348] The circuit board 900 has terminal 911 and circuit 912. Terminal 911 is connected to terminal 95 1. It is connected to terminal 952, antenna 914, antenna 915, and circuit 912. Multiple terminals 911 are provided, and each of the multiple terminals 911 is designated as a control signal input terminal and a power supply terminal. You can also refer to them as children.
[0349] Circuit 912 may be provided on the back surface of circuit board 900. Note that antenna 914 Furthermore, the antenna 915 is not limited to a coil shape, but may be, for example, linear or plate-shaped. Planar antenna, aperture antenna, traveling wave antenna, EH antenna, magnetic field antenna, dielectric You may use an antenna such as a body antenna. Alternatively, you may use antenna 914 or antenna 915. This may be a flat conductor. This flat conductor functions as one of the conductors for electric field coupling. This is possible. In other words, as one of the two conductors of the capacitor, A Antenna 914 or antenna 915 may be activated. This will create an electromagnetic field, a magnetic field. Furthermore, it is also possible to exchange power using an electric field.
[0350] The line width of antenna 914 is preferably larger than the line width of antenna 915. This allows for a greater amount of power to be received by antenna 914.
[0351] The secondary battery has a layer 916 between antennas 914 and 915 and the secondary battery 913. The layer 916 has the function of shielding electromagnetic fields, for example, from secondary batteries 913. It has the following properties. For layer 916, for example, a magnetic material can be used.
[0352] Note that the structure of the secondary battery is not limited to that shown in Figure 18.
[0353] For example, as shown in Figures 19A and 19B, the secondary battery 9 shown in Figures 18A and 18B Of the 13, antennas may be provided on each of the opposing pairs of faces. Figure 19A shows the above. Figure 19B is an external view showing one of a pair of surfaces, and Figure 19B is an external view showing the other of the pair of surfaces. That is the case. Furthermore, the same parts as the secondary battery shown in Figures 18A and 18B are as shown in Figures 18A and 18B. The explanation of the secondary battery shown in Figure 18B can be used as appropriate.
[0354] As shown in Figure 19A, an antenna is formed by sandwiching a layer 916 between one of the pair of surfaces of the secondary battery 913. A layer 917 is provided on the other side of the pair of sides of the secondary battery 913, as shown in Figure 19B. An antenna 918 is provided on either side of it. Layer 917 is an electromagnetic field, for example, from a secondary battery 913. It has the function of being able to shield. For layer 917, for example, a magnetic material can be used. can.
[0355] By adopting the above structure, the size of both antenna 914 and antenna 918 can be increased. It can be done. Antenna 918 can, for example, perform data communication with external devices. It has the ability to do so. Antenna 918 has a shape that can be applied to, for example, antenna 914. An antenna can be applied. Communication method between the secondary battery and other devices via antenna 918. In terms of the formula, it is used between a rechargeable battery and other devices, such as NFC (Near Field Communication). A variety of response methods can be applied.
[0356] Alternatively, as shown in Figure 19C, a display device may be connected to the secondary battery 913 shown in Figures 18A and 18B. A terminal 920 may be provided. The display device 920 is electrically connected to terminal 911. A label 910 does not need to be provided in the area where the display device 920 is provided. For the same part as the secondary battery shown in Figure 18B, the secondary battery shown in Figures 18A and 18B Explanations can be used as appropriate.
[0357] The display device 920 may display, for example, an image indicating whether or not it is charging, an image indicating the amount of stored power, etc. It may be displayed. The display device 920 may be, for example, electronic paper, liquid crystal display device, etc. A trollescent (also known as EL) display device can be used. For example, an electronic paper By using a supercharger, the power consumption of the display device 920 can be reduced.
[0358] Alternatively, as shown in Figure 19D, the sensor 9 is connected to the secondary battery 913 shown in Figures 18A and 18B. 21 may be provided. Sensor 921 is electrically connected to terminal 911 via terminal 922. The same parts as the secondary battery shown in Figures 18A and 18B are as shown in Figures 18A and 18B. The explanation of secondary batteries shown in Figure 18B can be used as appropriate.
[0359] Sensor 921 can measure, for example, displacement, position, velocity, acceleration, angular velocity, rotational speed, distance, Light, liquid, magnetism, temperature, chemicals, sound, time, hardness, electric field, electric current, voltage, power, radiation, It should have the ability to measure flow rate, humidity, gradient, vibration, odor, or infrared radiation. i. By providing the sensor 921, for example, data indicating the environment in which the secondary battery is placed can be obtained. It can also detect parameters (such as temperature) and store them in the memory within circuit 912.
[0360] Furthermore, an example of the structure of secondary battery 913 will be explained using Figure 20.
[0361] The secondary battery 913 shown in Figure 20A has terminals 951 and 952 inside the housing 930. It has a wound body 950. The wound body 950 is impregnated with an electrolyte inside the housing 930. Terminal 952 is in contact with the housing 930, and terminal 951 is in contact with the housing by using an insulating material or the like. It is not in contact with 930. Note that in Figure 20A, for convenience, the housing 930 is shown separately. However, in reality, the wound body 950 is covered by the housing 930, and terminals 951 and 952 are covered by the housing. It extends outside the body 930. The housing 930 is made of a metal material (for example, aluminum). ) or resin materials can be used.
[0362] Furthermore, as shown in Figure 20B, the housing 930 shown in Figure 20A is formed from multiple materials. This is also possible. For example, the secondary battery 913 shown in Figure 20B has housings 930a and 930b attached to it. The components are joined together, and the winding body 950 is provided in the area enclosed by the housing 930a and housing 930b. It is being done.
[0363] For the enclosure 930a, insulating materials such as organic resins can be used. In particular, the antenna By using a material such as organic resin on the surface where the na is formed, the electric field produced by the secondary battery 913 is created. This can suppress shielding. If the shielding of the electric field by the housing 930a is small, the housing 930a Antennas such as antenna 914 and antenna 915 may be installed inside the enclosure 930b. For example, metal materials can be used.
[0364] Furthermore, the structure of the wound body 950 is shown in Figure 21. The wound body 950 consists of a negative electrode 931 and It has a positive electrode 932 and a separator 933. The wound body 950 sandwiches the separator 933. Then the negative electrode 931 and the positive electrode 932 are stacked on top of each other, and the stacked sheet is wound up. It is a body. Furthermore, the stacking of the negative electrode 931, the positive electrode 932, and the separator 933 is further Multiple layers can be stacked.
[0365] The negative electrode 931 is connected to terminal 911 shown in Figure 18 via either terminal 951 or terminal 952. The positive terminal 932 is connected to terminal 951 and the other terminal of terminal 952, as shown in Figure 18. It connects to 11.
[0366] By using the positive electrode active material described in the previous embodiment for the positive electrode 932, high capacity cycling is achieved. This allows for the creation of a secondary battery 913 with excellent performance characteristics.
[0367] [Laminated rechargeable battery] Next, an example of a laminate-type secondary battery will be explained with reference to Figures 22 to 26. If a laminate-type secondary battery has a flexible structure, the number of flexible parts can be reduced. If implemented in electronic devices that also possess some of these features, the secondary battery will also bend in accordance with the deformation of the electronic device. It's also possible.
[0368] Using Figure 22, we will explain the laminated type secondary battery 980. The next battery 980 has a wound body 993 as shown in Figure 22A. The wound body 993 is connected to the negative electrode 994 and It has a positive electrode 995 and a separator 996. The winding body 993 is a winding as explained in Figure 21 Similar to the rotating body 950, the negative electrode 994 and the positive electrode 995 overlap with the separator 996 in between. These are laminated sheets, and the laminated sheets are then rolled up.
[0369] The number of layers in the stack consisting of the negative electrode 994, positive electrode 995, and separator 996 is required. The design should be appropriate depending on the capacitance and element volume. The negative electrode 994 is connected to the lead electrode 997 and One end of electrode 998 is connected to a negative electrode current collector (not shown), and positive electrode 995 is connected to a lead The electrode 997 and the other lead electrode 998 are connected to a positive electrode current collector (not shown). .
[0370] As shown in Figure 22B, there is a film 981 that forms the outer casing and a film 982 having a recess. The aforementioned wound body 993 is housed in a space formed by bonding the two together by heat pressing or the like. Thus, a secondary battery 980 can be manufactured as shown in Figure 22C. The wound body 993 is It has lead electrodes 997 and lead electrodes 998, and a film 981 and a film having a recess It is impregnated with electrolyte inside the Rum 982.
[0371] Film 981 and film 982 having a recess are made of a metal material such as aluminum. Materials and resins can be used. Film 981 and film 982 having recesses If a resin material is used as the material, when an external force is applied, the film 981 and the recess will be affected. The film 982 having the property can be deformed, and a flexible storage battery can be manufactured. It is possible.
[0372] Furthermore, Figures 22B and 22C show examples using two films, but one film is also available. A space is formed by folding the film, and the aforementioned wound body 993 is housed in that space. You may put it in.
[0373] By using the positive electrode active material described in the previous embodiment for the positive electrode 995, high capacity cycling is achieved. This allows for the creation of a secondary battery 980 with excellent performance characteristics.
[0374] Figure 22 also shows a secondary battery having a wound body in a space formed by a film that serves as the outer casing. I have explained the example of 980, but for example, as shown in Figure 23, the shape is formed by the film that forms the outer casing. In the resulting space, it can also be used as a secondary battery having multiple strip-shaped positive electrodes, separators, and negative electrodes. good.
[0375] The laminate-type secondary battery 500 shown in Figure 23A consists of a positive electrode current collector 501 and a positive electrode active material. A positive electrode 503 having a layer 502, and a negative electrode having a current collector 504 and a negative electrode active material layer 505. It has an electrode 506, a separator 507, an electrolyte 508, and an outer casing 509. A separator 507 is installed between the positive electrode 503 and the negative electrode 506 located within 509. Furthermore, the inside of the outer casing 509 is filled with electrolyte 508. The electrolyte 508 contains the following: The electrolyte shown in Form 2 can be used.
[0376] In the laminate-type secondary battery 500 shown in Figure 23A, the positive electrode current collector 501 and the negative electrode The current collector 504 also serves as a terminal for obtaining electrical contact with the outside. Therefore, the positive electrode is concentrated A portion of the current collector 501 and the negative electrode current collector 504 is arranged to be exposed to the outside from the outer casing 509. It may also be placed outside the casing 509. Without exposing the side, lead electrodes are used to connect the lead electrodes to the positive electrode current collector 501, or the negative electrode current collector. The lead electrodes may be exposed to the outside by ultrasonic bonding with the electrostatic body 504.
[0377] In the laminated secondary battery 500, the outer casing 509 is made of, for example, polyethylene, On a film made of materials such as polypropylene, polycarbonate, ionomer, and polyamide, A thin film of a highly flexible metal such as aluminum, stainless steel, copper, or nickel is provided, and further, An insulating synthetic material such as polyamide resin or polyester resin is used as the outer surface of the exterior body on a thin metal film. A three-layer laminate film with a resin film can be used.
[0378] Furthermore, an example of the cross-sectional structure of the laminate-type secondary battery 500 is shown in Figure 23B. For simplicity, the example shown consists of two current collectors, but in reality, as shown in Figure 23B... It is composed of multiple electrode layers.
[0379] In Figure 23B, the number of electrode layers is set to 16 as an example. The secondary battery 500 is also flexible. In Figure 23B, the negative electrode current collector 504 has 8 layers, and the positive electrode current collector The electrical body 501 has a structure of 16 layers in total, consisting of 8 layers. Figure 23B shows the negative electrode extraction section. This shows a cross-section, where eight layers of negative electrode current collectors 504 are ultrasonically bonded. Of course, the number of electrode layers The number is not limited to 16; it can be more or less. If the number of electrode layers is large, It can be made into a secondary battery with a large capacity. Also, if the number of electrode layers is small, it can be made thin. This allows for the creation of a rechargeable battery that can be molded and possesses excellent flexibility.
[0380] Here, an example of the external view of the laminate-type secondary battery 500 is shown in Figures 24 and 25. Figures 24 and 25 show the positive electrode 503, negative electrode 506, separator 507, casing 509, and positive electrode ri It has a lead electrode 510 and a negative lead electrode 511.
[0381] Figure 26A shows the external view of the positive electrode 503 and the negative electrode 506. The positive electrode 503 is the positive electrode current collector 501 The positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. 03 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as the tab region). Negative electrode 5 06 has a negative electrode current collector 504, and the negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. Furthermore, the negative electrode 506 is the region where the negative electrode current collector 504 is partially exposed, i.e., the tab region. It has the following characteristics. The area and shape of the tab regions of the positive and negative electrodes are not limited to the example shown in Figure 26A. stomach.
[0382] [Method for manufacturing laminated rechargeable batteries] Here, an example of a method for manufacturing a laminate-type secondary battery, whose external view is shown in Figure 24, is shown in Figure 2. This will be explained using Figure 26C, section 6B.
[0383] First, the negative electrode 506, separator 507, and positive electrode 503 are stacked. They are stacked as shown in Figure 26B. The negative electrode 506, separator 507, and positive electrode 503 are shown. Here, there are 5 sets of negative electrodes and 4 sets of positive electrodes. An example of how to use them together is shown. Next, the joining of the tab regions of the positive electrode 503 and the tab region of the outermost positive electrode. The positive lead electrode 510 is joined to the region. For joining, ultrasonic welding or the like can be used. Similarly, the bonding of the tab regions of the negative electrode 506 and the negative electrode lead to the tab region of the outermost negative electrode. The electrode 511 is joined.
[0384] Next, the negative electrode 506, separator 507, and positive electrode 503 are placed on the outer casing 509.
[0385] Next, as shown in Figure 26C, fold the outer casing 509 at the part indicated by the dashed line. The outer periphery of the exterior body 509 is joined. For joining, for example, heat compression bonding may be used. At this time, To allow the electrolyte 508 to be added later, a part (or one side) of the outer casing 509 is made in contact with the surface. A non-connected area (hereinafter referred to as the inlet) is provided.
[0386] Next, the electrolyte 508 (not shown) is introduced through the inlet provided in the outer casing 509. Introduce into the inside of 509. Introduce electrolyte 508 under reduced pressure or inert atmosphere. It is preferable to do so. And finally, the inlet is joined. In this way, the laminate It is possible to manufacture a secondary battery of type 500.
[0387] By using the positive electrode active material described in the previous embodiment for the positive electrode 503, high capacity cycling is achieved. This allows for the creation of a secondary battery 500 with excellent performance characteristics.
[0388] [Bendable rechargeable battery] Next, an example of a bendable secondary battery will be described with reference to Figures 27 and 28. ru.
[0389] Figure 27A shows a schematic top view of a bendable secondary battery 250. Figures 27B and 2 Figures 7C and 27D show the cutting lines C1-C2, C3-C4, and cutting line in Figure 27A, respectively. This is a schematic cross-sectional view of A1-A2. The secondary battery 250 consists of an outer casing 251 and an outer casing 25 It has a positive electrode 211a and a negative electrode 211b housed inside 1. The positive electrode 211a and electrical Lead 212a connected to the negative electrode 211b, and lead 212b electrically connected to the negative electrode 211b. It extends to the outside of the outer casing 251. Also, the region enclosed by the outer casing 251 contains positive electrode 2 In addition to 11a and the negative electrode 211b, an electrolyte (not shown) is sealed inside.
[0390] The positive electrode 211a and negative electrode 211b of the secondary battery 250 will be explained using Figure 28. Figure 28A explains the stacking order of the positive electrode 211a, the negative electrode 211b, and the separator 214. This is a perspective view. Figure 28B shows the positive electrode 211a and the negative electrode 211b, as well as the lead 21 This is a perspective view showing lead 2a and lead 212b.
[0391] As shown in Figure 28A, the secondary battery 250 has multiple strip-shaped positive electrodes 211a, multiple strips It has a negative electrode 211b and a plurality of separators 214. Positive electrode 211a and negative electrode 21 Each 1b has a protruding tab portion and a portion other than the tab. One side of the positive electrode 211a A positive electrode active material layer is formed on the part other than the tab of the negative electrode 211b, and on the part other than the tab on one side of the negative electrode 211b A negative electrode active material layer is formed.
[0392] The sides of the positive electrode 211a that do not have a positive electrode active material layer formed on them, and the negative electrode active The positive electrode 211a and the negative electrode 211b are stacked so that their surfaces, which do not have any material formed on them, are in contact with each other. It will be done.
[0393] Furthermore, the surface on which the positive electrode active material of the positive electrode 211a is formed and the surface on which the negative electrode active material of the negative electrode 211b is formed A separator 214 is provided between the surfaces. In Figure 28, the separator is shown for clarity. Route 214 is indicated by a dotted line.
[0394] Also, as shown in Figure 28B, the multiple positive electrodes 211a and leads 212a are connected at the joint 215a They are electrically connected at the joint 21. Electrically connected at 5b.
[0395] Next, the outer casing 251 will be explained using Figures 27B, 27C, 27D, and 27E. ru.
[0396] The outer casing 251 has a film-like shape and sandwiches the positive electrode 211a and the negative electrode 211b. It is folded in half. The outer casing 251 has a folded portion 261 and a pair of sealing portions It has a 262 and a sealing portion 263. The pair of sealing portions 262 are positive electrode 211a and It is provided on either side of the negative electrode 211b and can also be called a side seal. Also, seal portion 2 Section 63 has a portion that overlaps with leads 212a and 212b, and is also called the top seal. It is possible.
[0397] The outer casing 251 has ridges 271 and valleys in the portion that overlaps with the positive electrode 211a and the negative electrode 211b. It is preferable that the 272 have a wave shape arranged alternately. Also, the sealing portion 2 of the outer casing 251 It is preferable that 62 and the sealing portion 263 are flat.
[0398] Figure 27B shows a cross-section cut at the point where it overlaps with ridge line 271, and Figure 27C shows the valley line 272 Figures 27B and 27C both show the secondary battery 250 and the positive This corresponds to the cross-section in the width direction of pole 211a and negative pole 211b.
[0399] Here, the ends in the width direction of the positive electrode 211a and the negative electrode 211b, that is, the positive electrode 211a and The distance La is defined as the distance between the end of the negative electrode 211b and the seal portion 262. Secondary battery 25 When deformation such as bending is applied, the positive electrode 211a and the negative electrode 211b are as described later. They deform so that they are offset from each other in the longitudinal direction. In this case, if the distance La is too short, the outer casing 251 In some cases, the positive electrode 211a and the negative electrode 211b rub strongly against each other, causing damage to the outer casing 251. Yes. In particular, when the metal film of the outer casing 251 is exposed, the metal film is affected by the electrolyte. There is a risk of corrosion. Therefore, it is preferable to set the distance La as long as possible. That's true. On the other hand, if the distance La is made too large, the volume of the secondary battery 250 will increase. .
[0400] Furthermore, the thicker the combined thickness of the stacked positive electrode 211a and negative electrode 211b, the greater the positive electrode 21 It is preferable to increase the distance La between 1a and the negative electrode 211b and the seal portion 262. stomach.
[0401] More specifically, stacked positive electrode 211a and negative electrode 211b and (not shown) separate When the total thickness of 214 is t, the distance La is between 0.8 and 3.0 times the thickness t. Preferably, the ratio is 0.9 times or more and 2.5 times or less, more preferably 1.0 times or more and 2.0 times or less. It is preferable that the distance La is within this range, making it compact and resistant to bending. This enables the creation of highly reliable batteries.
[0402] Furthermore, when the distance between the pair of sealing portions 262 is denoted as distance Lb, distance Lb is set to the positive electrode 211 Make it sufficiently larger than the width of a and the negative electrode 211b (here, the width Wb of the negative electrode 211b). This is preferable. This allows the secondary battery 250 to be subjected to repeated bending or other deformations. Even if the positive electrode 211a and the negative electrode 211b come into contact with the outer casing 251, the positive electrode 211a and Because a portion of the negative electrode 211b can be shifted in the width direction, the positive electrode 211a and the negative electrode 211 This effectively prevents friction between b and the outer casing 251.
[0403] For example, the difference between the distance Lb between the pair of sealing portions 262 and the width Wb of the negative electrode 211b is positive. The thickness t of electrode 211a and negative electrode 211b is 1.6 times or more and 6.0 times or less, preferably 1.8 It is preferable that the ratio be between 2.0 and 4.0 times, and more preferably between 2.0 and 4.0 times. stomach.
[0404] In other words, it is desirable that the distance Lb, width Wb, and thickness t satisfy the relationship shown in equation 2 below. It seems so.
[0405]
number
[0406] Here, a is 0.8 or more and 3.0 or less, preferably 0.9 or more and 2.5 or less, more preferably The value of 'k' satisfies 1.0 or greater and 2.0 or less.
[0407] Furthermore, Figure 27D is a cross-section including lead 212a, and the secondary battery 250, positive electrode 211a This corresponds to the longitudinal cross-section of the negative electrode 211b. As shown in Figure 27D, the bent portion 26 In 1, between the longitudinal ends of the positive electrode 211a and the negative electrode 211b and the outer casing 251 It is preferable to have a space 273.
[0408] Figure 27E shows a schematic cross-sectional view of the secondary battery 250 when it is bent. This corresponds to the cross-section at the cutting line B1-B2 in 27A.
[0409] When the secondary battery 250 is bent, a portion of the outer casing 251 located on the outside of the bend stretches inwards. Other parts located there deform to shrink. More specifically, the parts located on the outside of the outer casing 251 The part deforms so that the wave amplitude is small and the wave period is large. On the other hand, the outer body The portion located inside 251 is modified so that the wave amplitude is large and the wave period is small. Shape. In this way, the outer casing 251 deforms, and as it bends, the outer casing 251 Because the stress is relieved, the material that makes up the exterior 251 does not need to expand or contract. As a result, the outer casing 251 does not get damaged, and the secondary battery 250 can be bent with a small force. can.
[0410] Also, as shown in Figure 27E, when the secondary battery 250 is bent, the positive electrode 211a and the negative electrode 2 11b and the other are relatively shifted. At this time, multiple stacked positive electrodes 211a and negative electrodes are shifted. Since one end of pole 211b on the sealing portion 263 side is fixed by the fixing member 217, it is not foldable. Each part shifts such that the amount of shift increases the closer it is to the recessed part 261. As a result, the positive electrode 2 The stress on 11a and the negative electrode 211b is relieved, and the positive electrode 211a and the negative electrode 211b themselves The body does not need to expand or contract. As a result, the positive electrode 211a and the negative electrode 211b are not damaged. The 250 secondary battery can be bent.
[0411] Furthermore, there is a space 273 between the positive electrode 211a and the negative electrode 211b and the outer casing 251. By doing so, the positive electrode 211a and negative electrode 211b, which are located on the inside when bent, are positioned within the outer casing 25 It can shift relative to point 1 without making contact.
[0412] The secondary battery 250 illustrated in Figures 27 and 28 can withstand repeated bending and straightening, and the external Damage to the casing, damage to the positive electrode 211a and negative electrode 211b are less likely to occur, and battery characteristics do not deteriorate. It is a battery that is difficult to use. The positive electrode 211a of the secondary battery 250 is as described in the previous embodiment. By using a positive electrode active material, it is possible to create a battery with even better cycle characteristics.
[0413] Figure 29A shows three laminated rechargeable batteries 500 connected to a first plate 521 and a second plate. This is a perspective view showing how it is sandwiched and fixed between rate 524. As shown in Figure 29B, it is fixed. Using fixture 525a and fixing fixture 525b, the first plate 521 and the second plate 5 By fixing the distance between 24 and the battery, three secondary batteries 500 can be pressurized.
[0414] Figures 29A and 29B show an example using three laminate-type 500 rechargeable batteries. However, it is not particularly limited, and it is also possible to use four or more 500 rechargeable batteries, or ten or more. If used in quantities of 100 or more, it can be used as a power source for small vehicles, and if used in quantities of 100 or more, it can be used as a large power source for vehicles. It can also be used as a power source. Furthermore, it includes protection circuits to prevent overcharging and temperature rise monitoring. A temperature sensor for monitoring may be provided on the laminated secondary battery 500.
[0415] In all-solid-state batteries, by applying a predetermined pressure in the stacking direction of the stacked positive and negative electrodes, The contact state of the internal interface can be maintained in good condition. Applying pressure suppresses expansion in the stacking direction due to charging and discharging of all-solid-state batteries. This can be achieved, improving the reliability of all-solid-state batteries.
[0416] This embodiment can be used in appropriate combination with other embodiments.
[0417] (Embodiment 5) This embodiment describes an example of mounting a secondary battery, which is one aspect of the present invention, into an electronic device. I will reveal it.
[0418] First, as explained in part of Embodiment 3, a bendable secondary battery is mounted in an electronic device. Examples are shown in Figures 30A to 30G. Electronic devices using a bendable secondary battery and For example, television equipment (also called television or television receiver), computer Monitors for use with computers, digital cameras, digital video cameras, digital photo frames, etc. M, mobile phone (also called mobile phone or mobile phone device), portable game console, personal digital assistant, Examples include sound reproduction devices and large game machines such as pachinko machines.
[0419] Furthermore, rechargeable batteries with flexible shapes can be installed in the interior or exterior walls of houses and buildings, or in automatic It can also be integrated to conform to the curved surfaces of the car's interior or exterior.
[0420] Figure 30A shows an example of a mobile phone. The mobile phone 7400 is housed in a casing 7401. In addition to the built-in display unit 7402, there are operation buttons 7403, an external connection port 7404, and a speaker. It is equipped with a microphone 7405, microphone 7406, etc. Note that the mobile phone 7400 is a secondary battery It has a battery 7407. A secondary battery according to one embodiment of the present invention is used for the above secondary battery 7407. This allows us to provide lightweight and long-lasting mobile phones.
[0421] Figure 30B shows the mobile phone 7400 in a curved state. Mobile phone 7400 When the entire structure is bent by an external force, the secondary battery 7 located inside it is revealed. The 407 is also bent. Figure 30C shows the state of the bent secondary battery 7407 at that time. The 7407 secondary battery is a thin rechargeable battery. The 7407 secondary battery is fixed in a bent state. It is done. Furthermore, the secondary battery 7407 has lead electrodes electrically connected to the current collector. Yes, for example, the current collector is made of copper foil, and part of it is alloyed with gallium, and the active material that comes into contact with the current collector This improves adhesion to the structural layer, resulting in a configuration that ensures high reliability even when the secondary battery 7407 is bent. It is.
[0422] Figure 30D shows an example of a bangle-type display device. The portable display device 7100 is housed in a casing. It comprises a body 7101, a display unit 7102, operation buttons 7103, and a secondary battery 7104. Figure 30E shows the state of the bent secondary battery 7104. The secondary battery 7104 is bent. When worn on the user's arm in this state, the casing deforms, causing part or all of the secondary battery 7104 to be damaged. The curvature changes. The degree of curvature at any point on the curve can be expressed using the radius of the corresponding circle. The resulting value is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, if the radius of curvature is 40 Within a range of 150 mm or more, a portion or all of the main surface of the housing or secondary battery 7104 The part changes. The radius of curvature on the main surface of secondary battery 7104 is 40 mm or more and 150 mm or less. Within the following range, high reliability can be maintained. The above secondary battery 7104 is an embodiment of the present invention. By using a rechargeable battery, a lightweight and long-lasting portable display device can be provided.
[0423] Figure 30F shows an example of a wristwatch-type personal information terminal. The personal information terminal 7200 is... Housing 7201, display unit 7202, band 7203, buckle 7204, operation button 720 5. It is equipped with input / output terminals 7206, etc.
[0424] The 7200 mobile information terminal offers mobile phone calls, email, document viewing and creation, music playback, and more. It can run various applications such as internet communication and computer games. Cut.
[0425] The display unit 7202 has a curved display surface, and displays information along the curved surface. It is possible to do so. In addition, the display unit 7202 is equipped with a touch sensor, and the screen can be touched with a finger or stylus. It can be operated by touching it. For example, icon 7 displayed on display unit 7202 Touching 207 will launch the application.
[0426] The 7205 control button is used for time setting, as well as power on / off, wireless communication on, and more. Various functions such as operation, activation and deactivation of silent mode, and activation and deactivation of power saving mode. It can be made to hold. For example, the operating system built into the personal digital assistant 7200 The system also allows you to freely configure the function of the control button 7205.
[0427] Furthermore, the 7200 portable information terminal is capable of performing standardized short-range wireless communication. For example, by communicating with a wireless headset, hands-free operation is possible. You can also make calls.
[0428] Furthermore, the portable information terminal 7200 is equipped with an input / output terminal 7206, and can connect to other information terminals. Data can be exchanged directly via this. Also, charging is possible via input / output terminal 7206. It can also perform electrical operations. Note that charging is done wirelessly without using input / output terminal 7206. You may go.
[0429] The display unit 7202 of the portable information terminal 7200 has a secondary battery according to one aspect of the present invention. By using a secondary battery according to one aspect of the present invention, a lightweight and long-lasting portable information terminal can be provided. For example, the secondary battery 7104 shown in Figure 30E is placed inside the housing 7201 in a curved state. Alternatively, it can be incorporated into the band 7203 in a flexible state.
[0430] The personal information terminal 7200 preferably has a sensor. For example, a fingerprint sensor. Human body sensors such as pulse sensors and body temperature sensors, as well as touch sensors, pressure sensors, and accelerometers. It is preferable that sensors, etc., be installed.
[0431] Figure 30G shows an example of an armband-type display device. The display device 7300 has a display unit 73 The present invention has a secondary battery having 04. The display device 7300 also has a display Part 7304 can also be equipped with a touch sensor, and it can also function as a portable information terminal. It can also be done this way.
[0432] The display unit 7304 has a curved display surface, and displays are performed along the curved display surface. This is possible. In addition, the display device 7300 can display information via standardized short-range wireless communication. The situation can be changed.
[0433] Furthermore, the display device 7300 is equipped with input / output terminals and can be directly connected to other information terminals via connectors. It can exchange data. It can also be charged via its input / output terminals. Furthermore, charging may be performed wirelessly without using input / output terminals.
[0434] By using a secondary battery according to one aspect of the present invention as the secondary battery of the display device 7300, We can provide lightweight and long-lasting display devices.
[0435] Furthermore, an example of mounting the secondary battery with good cycle characteristics shown in the previous embodiment into an electronic device is provided. This will be explained using Figures 30H, 31, and 32.
[0436] By using a secondary battery according to one aspect of the present invention as a secondary battery for everyday electronic devices, a lightweight and long-lasting battery can be obtained. We can provide essential products. For example, everyday electronic devices such as electric toothbrushes and electric shavers. Examples include electric beauty devices, and the rechargeable batteries for these products are designed to be easy for the user to hold. The idea is to create a rechargeable battery that is small, lightweight, and high-capacity, with a stick-like shape.
[0437] Figure 30H is a perspective view of a device also known as a tobacco-containing smoking device (electronic cigarette). In 0H, the e-cigarette 7500 includes an atomizer 7501 containing a heating element, and an atomizer The rechargeable battery 7504 that supplies power, and a cartridge containing a liquid supply bottle and sensors, etc. It consists of 7502. To enhance safety, overcharging and over-discharging of the secondary battery 7504 are controlled. A protective circuit to prevent this may be electrically connected to the secondary battery 7504. (Secondary battery shown in Figure 30H) The 7504 has an external terminal so that it can be connected to a charging device. The rechargeable battery 7504 has Since this will be the tip in that case, it is desirable that the total length be short and the weight be light. i. A secondary battery according to one aspect of the present invention has high capacity and good cycle characteristics, and therefore can be used over a long period of time. This allows us to offer the 7500, a small and lightweight e-cigarette that can be used for extended periods.
[0438] Next, Figures 31A and 31B show an example of a foldable tablet device. The tablet terminal 9600 shown in Figures 31A and 31B consists of a housing 9630a and a housing 963 0b, movable part 9640 connecting housing 9630a and housing 9630b, display unit 9631a and Display unit 9631 having display unit 9631b, switches 9625 to 9627, retainer It has a fastener 9629 and an operating switch 9628. The display unit 9631 has flexibility By using a panel, a tablet device with a larger display area can be created. (Figure) Figure 31A shows the tablet terminal 9600 in an open state, and Figure 31B shows the tablet terminal This indicates that the last 9600 is closed.
[0439] Furthermore, the tablet terminal 9600 stores inside the housings 9630a and 9630b. It has an electric body 9635. The electric body 9635 passes through the movable part 9640 and through the housing 9630a and the casing. It is provided across body 9630b.
[0440] The display unit 9631 can have all or part of its area designated as a touch panel area, and By touching the image, text, input form, etc., including the icon displayed in that area, data can be collected. Input can be made. For example, keys can be placed on the entire surface of the display unit 9631a on the housing 9630a. The board buttons are displayed, and information such as text and images is shown on the display unit 9631b on the chassis 9630b. It may also be used to display information.
[0441] Furthermore, the keyboard is displayed on the display unit 9631b on the chassis 9630b side, and the chassis 9630 The display unit 9631a on side a may be used to display information such as characters and images. The touch panel keyboard display switching button is displayed in section 9631, By touching the button with a finger or stylus, the keyboard will be displayed on the display unit 9631. You can do that.
[0442] Furthermore, the touch panel area of the display unit 9631a on the housing 9630a side and the housing 9630b side It is also possible to simultaneously input touch input to the touch panel area of the display unit 9631b.
[0443] Furthermore, switches 9625 to 9627 operate the tablet terminal 9600. It's not just an interface for doing that, but also an interface that allows you to switch between various functions. - It may also be a face. For example, at least of switch 9625 to switch 9627 One of them functions as a switch to turn the power of the tablet device 9600 on and off. It is also possible that, for example, at least one of switches 9625 to 9627 is vertical A function to switch the display orientation, such as horizontal or horizontal display, or to switch between black and white and color display. It may also have a function to enable. Also, for example, at least one of switches 9625 to 9627 Furthermore, the display unit 963 may have a function to adjust the brightness of the display unit 9631. The brightness of 1 is detected by the light sensor built into the tablet device 9600 during use. It can be optimized according to the amount of light. Note that tablet devices use light sensors. In addition, it incorporates other detection devices such as gyroscopes, accelerometers, and other sensors that detect tilt. You may allow it.
[0444] Furthermore, Figure 31A shows the display unit 9631a on the housing 9630a side and the display unit on the housing 9630b side The example shows that the display area of 9631b is almost the same as that of display unit 9631a and display unit 96 The display area of each of the 31b is not particularly limited, and the size of one and the size of the other may differ. They may be present, and the display quality may also differ. For example, one may have a higher resolution display than the other. It can also be used as a display panel that can perform various operations.
[0445] Figure 31B shows the tablet terminal 9600 in a folded state. The terminal 9600 includes a housing 9630, a solar cell 9633, and a DC-DC converter 9636. It has a charge / discharge control circuit 9634. Furthermore, as the energy storage body 9635, according to one aspect of the present invention Use an energy storage device.
[0446] As mentioned above, the 9600 tablet can be folded in half, so when not in use... The casings 9630a and 9630b can be folded so that they overlap. By folding it, the display unit 9631 can be protected, thus improving the durability of the tablet terminal 9600. Durability can be improved. Furthermore, the energy storage body 9635 using a secondary battery according to one aspect of the present invention is Due to its high capacity and good cycle characteristics, this tablet can be used for extended periods of time. We can provide the 9600 type terminal.
[0447] In addition, the tablet terminal 9600 shown in Figures 31A and 31B has various other features. Features that display information (still images, videos, text images, etc.), calendar, date or time. Functions that display such information on the display unit, and touch input operations or editing of the information displayed on the display unit. It has features such as input functionality and the ability to control processing through various software (programs). It is possible.
[0448] The solar cell 9633 attached to the surface of the tablet device 9600 provides power to the tablet. It can be supplied to the control panel, display unit, or video signal processing unit, etc. Note that the solar cell 96 33 can be provided on one or both sides of the housing 9630, and efficiently charges the energy storage unit 9635. This configuration can be implemented in a specific way. Note that the energy storage unit 9635 is a lithium-ion battery. Using it offers advantages such as enabling miniaturization.
[0449] Furthermore, the configuration and operation of the charge / discharge control circuit 9634 shown in Figure 31B are shown in Figure 31C. A block diagram will be shown and explained. Figure 31C shows the solar cell 9633, the energy storage unit 9635, and the DCD. C converter 9636, converter 9637, switches SW1 to SW3, display unit 963 Regarding 1, it shows the energy storage unit 9635, the DC-DC converter 9636, and the converter 96 37. Switches SW1 to SW3 correspond to the charge / discharge control circuit 9634 shown in Figure 31B. This will be the location.
[0450] First, let's explain an example of how the solar cell 9633 operates when generating electricity using ambient light. The electricity generated by the solar cells is converted into a DC-DC converter to provide the voltage necessary to charge the 9635 energy storage unit. The converter 9636 performs voltage boosting or bucking. Then, the solar power is used to control the operation of the display unit 9631. When power from pond 9633 is used, switch SW1 is turned ON, and converter 963 In step 7, the voltage is increased or decreased to the required voltage for the display unit 9631. Also, the display unit 963 If you do not want to display in step 1, turn SW1 off and turn SW2 on to enable the storage unit 9635. The configuration should include charging capabilities.
[0451] While solar cell 9633 is shown as an example of a power generation method, it is not particularly limited to this method. Storage using other power generation methods such as piezoelectric elements (piezo elements) and thermoelectric elements (Peltier elements) The configuration may also involve charging the battery 9635. For example, power may be transmitted and received wirelessly (contactlessly). This includes contactless power transmission modules that charge via this method, as well as configurations that combine this with other charging methods. You may do so.
[0452] Figure 32 shows an example of another electronic device. In Figure 32, the display device 8000 is the present invention. This is an example of an electronic device using a secondary battery 8004 according to one embodiment. Specifically, the display device 80 00 corresponds to a display device for receiving TV broadcasts, and consists of a housing 8001, a display unit 8002, and a speaker. It has a part 8003, a secondary battery 8004, etc. A secondary battery 8004 according to one aspect of the present invention is It is located inside the enclosure 8001. The display device 8000 receives power from the commercial power supply. You can receive power from it, or you can use the power stored in the secondary battery 8004. Therefore, even when power cannot be supplied from the commercial power source due to a power outage or the like, according to one aspect of the present invention By using the secondary battery 8004 as an uninterruptible power supply, the display device 8000 can be used. Yes.
[0453] The display unit 8002 has light-emitting elements such as liquid crystal display devices and organic EL elements in each pixel. Optical devices, electrophoresis display devices, DMDs (Digital Micromirror Dev ice), PDP (Plasma Display Panel), FED (Field Semiconductor display devices such as Emission Displays can be used.
[0454] In addition to being used for receiving TV broadcasts, the display devices are also used for personal computers and for displaying advertisements. This includes all information display devices.
[0455] In Figure 32, the fixed lighting device 8100 is a secondary battery 8 according to one aspect of the present invention. This is an example of an electronic device using 103. Specifically, the lighting device 8100 has a housing 8101, It has a light source 8102, a secondary battery 8103, etc. In Figure 32, the secondary battery 8103 is located in the housing 8 For example, consider the case where 101 and the light source 8102 are installed inside the ceiling 8104. Although shown, the secondary battery 8103 may also be located inside the housing 8101. The device 8100 can receive power from a commercial power source, or from a secondary battery 8103. It is also possible to use stored power. Therefore, in the event of a power outage, etc., power supply from commercial power source Even when it is not possible to receive a power supply, the secondary battery 8103 according to one aspect of the present invention can be used as an uninterruptible power supply. This makes it possible to use the lighting device 8100.
[0456] In Figure 32, a fixed lighting device 8100 installed on the ceiling 8104 is shown as an example. However, in one aspect of the present invention, the secondary battery is located on the side wall 8105, floor, and other surfaces besides the ceiling 8104. It can also be used in fixed lighting devices installed in windows such as 8106 and 8107, and also in tables It can also be used in overhead lighting fixtures and other applications.
[0457] Furthermore, the light source 8102 can use an artificial light source that artificially obtains light using electricity. Yes, it is possible. Specifically, this includes discharge lamps such as incandescent light bulbs and fluorescent lamps, and LEDs and organic EL elements. Optical elements are an example of the artificial light sources mentioned above.
[0458] In Figure 32, the air conditioner having an indoor unit 8200 and an outdoor unit 8204 is This is an example of an electronic device using a secondary battery 8203 according to one aspect of the present invention. Specifically, the room The internal unit 8200 includes a housing 8201, an air outlet 8202, a secondary battery 8203, etc. (Figure 32) The example given is that the secondary battery 8203 is installed in the indoor unit 8200, but The next battery 8203 may be located in the outdoor unit 8204. Alternatively, it may be located in the indoor unit 8200 and the room The secondary battery 8203 may be provided on both sides of the outdoor unit 8204. - It can also receive power from the commercial power supply, or stored in the secondary battery 8203 Electricity can also be used. In particular, both the indoor unit 8200 and the outdoor unit 8204 can use secondary batteries 8 If 203 is installed, when power cannot be supplied from the commercial power source due to a power outage, etc. However, by using the secondary battery 8203 according to one aspect of the present invention as an uninterruptible power supply, Conditioner can be used.
[0459] Figure 32 shows a separate-type air conditioner consisting of an indoor unit and an outdoor unit. The example shown is an integrated air conditioner that has both the indoor and outdoor unit functions in a single housing. A secondary battery according to one aspect of the present invention can also be used in the conditioner.
[0460] In Figure 32, the electric refrigerator 8300 is a secondary battery 8304 according to one aspect of the present invention. This is an example of an electronic device using [a specific component]. Specifically, the electric refrigerator 8300 has a casing 8301, It has a refrigerator door 8302, a freezer door 8303, a secondary battery 8304, etc. In Figure 32, The secondary battery 8304 is located inside the casing 8301. The electric refrigerator 8300 is It can also receive power from the commercial power supply, or power stored in the secondary battery 8304 It is also possible to use this. Therefore, if power cannot be supplied from the commercial power source due to a power outage, etc. Even at times, by using the secondary battery 8304 according to one aspect of the present invention as an uninterruptible power supply, The 8300 refrigerator / freezer will become available for use.
[0461] Of the electronic devices mentioned above, high-frequency heating devices such as microwave ovens and electric rice cookers are included. Sub-devices require high power for short periods. Therefore, they need to supplement the power that cannot be supplied by the commercial power supply. By using a secondary battery according to one aspect of the present invention as an auxiliary power source to assist, electronic devices This prevents the commercial power circuit breaker from tripping when using it.
[0462] Furthermore, during periods when electronic devices are not in use, especially the total amount of electricity that can be supplied by the commercial power source... Of these, during the time periods when the proportion of electricity actually used (called the electricity usage rate) is low, By storing power in the secondary battery, the rate of power consumption outside of the above-mentioned time period is suppressed. It is possible. For example, in the case of the electric refrigerator 8300, when the temperature is low, the refrigerator door 83 02. At night when the freezer door 8303 is not opened or closed, power is supplied to the secondary battery 8304. Store. Then, as the temperature rises, the refrigerator door 8302 and the freezer door 8303 are opened and closed. During the daytime, by using the secondary battery 8304 as an auxiliary power source, daytime electricity usage The rate can be kept low.
[0463] According to one aspect of the present invention, the cycle characteristics of a secondary battery are improved, thereby enhancing reliability. This can be done. Furthermore, according to one aspect of the present invention, a high-capacity secondary battery can be made, and thus This improves the characteristics of secondary batteries, and therefore makes the secondary batteries themselves smaller and lighter. Therefore, a secondary battery, which is one aspect of the present invention, can be used in the electronic device described in this embodiment. By incorporating this technology, it becomes possible to create electronic devices with a longer lifespan and lighter weight.
[0464] This embodiment can be implemented in appropriate combination with other embodiments.
[0465] (Embodiment 6) This embodiment shows an example in which a secondary battery according to one aspect of the present invention is mounted on a vehicle.
[0466] When a secondary battery is installed in a vehicle, it can become a hybrid electric vehicle (HEV), an electric vehicle (EV), or This enables the realization of next-generation clean energy vehicles such as plug-in hybrid vehicles (PHEVs). ru.
[0467] Figure 33 illustrates a vehicle using a secondary battery, which is one embodiment of the present invention. Figure 33A shows The vehicle shown, model 8400, is an electric vehicle that uses an electric motor as its power source for driving. Alternatively, an electric motor and an engine may be appropriately selected and used as the power source for propulsion. This is a hybrid vehicle capable of [something]. By using one aspect of the present invention, a long driving range is achieved. A vehicle can be realized. Furthermore, the 8400 automobile has a secondary battery. The secondary battery is, The secondary battery modules shown in Figures 17C and 17D are arranged on the floor of the vehicle. You can use it. Also, a battery pack made by combining multiple secondary batteries as shown in Figure 20 can be placed on the floor inside the vehicle. It may be installed in part. The secondary battery not only drives the electric motor 8406, To supply power to light-emitting devices such as headlights 8401 and interior lights (not shown). It is possible.
[0468] Furthermore, the secondary battery is used in the speedometer, tachometer, and other displays of the 8400 automobile. It can supply power to the display device. Furthermore, the secondary battery powers the navigation system of the 8400 automobile. It can supply power to semiconductor devices such as gate systems.
[0469] The automobile 8500 shown in Figure 33B has a plug-in type secondary battery. It can be charged by receiving power from an external charging facility using methods such as contactless power supply. Figure 33B shows the secondary battery installed in the automobile 8500, powered by the ground-mounted charging device 8021. 8024 indicates that charging is taking place via cable 8022. During charging, Charging methods and connector specifications are determined by the specified methods such as CHAdeMO® or Combo. It can be done as appropriate. The charging device 8021 may also be a charging station installed in a commercial facility. It may also be a household power supply. For example, by plug-in technology, external power supply The power supply can charge the secondary battery 8024 installed in the vehicle 8500. This can be done by converting AC power to DC power via a conversion device such as an AC / DC converter. can.
[0470] Although not shown in the diagram, a power receiving device is mounted on the vehicle, and power is supplied wirelessly from a ground-based power transmission device. It can also be charged by supplying power. In this contactless power supply method, the power transmission equipment is installed on the road or exterior wall. By incorporating this, charging can be performed not only when the vehicle is stopped but also while it is in motion. The electric system may be used to transmit and receive power between vehicles. Furthermore, the exterior of the vehicle Solar panels may be installed to charge the secondary battery while the vehicle is stopped or in motion. Electromagnetic induction and magnetic resonance methods can be used to supply power in this environment.
[0471] Furthermore, Figure 33C shows an example of a two-wheeled vehicle using a secondary battery according to one embodiment of the present invention. The scooter 8600 shown includes a secondary battery 8602, side mirrors 8601, and turn signals 86 It is equipped with 03. The secondary battery 8602 can supply power to the turn signal light 8603. .
[0472] Furthermore, the scooter 8600 shown in Figure 33C has a secondary battery 8602 in the under-seat storage compartment 8604. It can store the secondary battery 8602 even if the under-seat storage 8604 is small. It can be stored in the under-seat storage compartment 8604. The secondary battery 8602 is removable. Therefore, when charging, the 8602 secondary battery is carried indoors, charged, and stored before driving. That's all you need to do.
[0473] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the capacity of the secondary battery is increased. This allows for miniaturization and weight reduction of the secondary battery itself. Making the unit itself smaller and lighter would contribute to reducing the vehicle's weight, thus improving its range. Yes, it is possible. Furthermore, the secondary battery installed in the vehicle can also be used as a power source for purposes other than the vehicle itself. In this case, for example, it is possible to avoid using commercial power during peak electricity demand. Therefore, if we can avoid using commercial power during peak electricity demand, we can save energy and It can contribute to reducing carbon dioxide emissions. Also, if the cycle characteristics are good, two Because the next battery can be used for a long period of time, the amount of rare metals used, including cobalt, can be reduced. It is possible.
[0474] This embodiment can be implemented in appropriate combination with other embodiments. [Examples]
[0475] <Fabrication of positive electrode active material> Referring to the flowchart in Figure 10, when the number of cobalt atoms is set to 100, magnesium, nickel The positive electrode active material was prepared so that the number of atoms of kel and aluminum were as shown in Table 1.
[0476] [Table 1]
[0477] First, a mixture containing magnesium and fluorine is prepared by steps S11 to S13. I prepared substance 902. The molar ratio of LiF to MgF2 is LiF:MgF2=1:3. The material was weighed, mixed, and ground using a dry method. Mixing and grinding were performed using zirconia balls. The process was carried out in a 7m mill at 150 rpm for 1 hour. The processed material was collected and mixed with mixture 902. did.
[0478] Next, we prepared Cellseed C-10N, manufactured by Nippon Chemical Industrial Co., Ltd., as a composite oxide. Step S24).
[0479] Next, mixture 902 and the composite oxide were mixed (step S31). If the number of cobalt atoms is set to 100, then the number of magnesium atoms in mixture 902 The quantities were weighed to match the values shown in Table 1. The mixing was done by dry mixing. The mixture was zirconia The process was performed using a ball mill with a ball bearing at 150 rpm for 1 hour.
[0480] Next, the processed material was recovered to obtain mixture 903 (step S32).
[0481] Next, the mixture 903 is placed in an alumina crucible and heated in an oxygen atmosphere muffle furnace at 850°C, 6 The material was annealed for 0 hours (step S33). During annealing, the alumina crucible was covered. The oxygen flow rate was set to 10 L / min. The heating rate was set to 200°C / hr, and the cooling rate was set to 10 hours or more. The process was carried out. The material after heat treatment was collected and sieved to obtain a second composite oxide (S Step S34).
[0482] Next, nickel is added as step S41, and steps S41 to S44 are repeated. Aluminum was added after several steps. Note that steps S41 to S44 were not performed. Samples were also prepared under different conditions.
[0483] First, nickel hydroxide, the metal source, and the second composite oxide were ball-milled. When the number of atoms of balt is set to 100, the number of atoms of nickel should be as shown in Table 1. Each was mixed separately. The mixing was done using a ball mill with zirconia balls at 150 rpm. The process was carried out for 1 hour. After mixing, the mixture was passed through a 300 μm diameter sieve. Then, the resulting mixture was agglutinated. The material was placed in a Mina crucible, covered, and annealed at 850°C for 2 hours in an oxygen atmosphere.
[0484] Next, a coating layer containing aluminum was formed by the sol-gel method. A was used as the metal source. l-isopropoxide was used, with 2-propanol as the solvent. Cobalt atom When the number is set to 100, the number of aluminum atoms is mixed to the values shown in Table 1. They were combined. Then, the resulting mixture was placed in an alumina crucible, covered, and heated in an oxygen atmosphere for 8 minutes. The mixture was annealed at 50°C for 2 hours. Afterward, it was sieved through a 53 μm diameter sieve to collect the powder, as shown in Table 1. Each positive electrode active material was obtained under the conditions shown. Of the obtained positive electrode active materials, magnesium Under the conditions that the number of atoms in um, nickel, and aluminum is 1, 0.5, and 0.5, respectively... The results of the particle size distribution measurement are shown in Figure 46.
[0485] <Manufacturing of secondary batteries> Each positive electrode was fabricated using the positive electrode active material obtained above. Positive electrode active material, A A slurry made by mixing B and PVDF as active materials in a ratio of AB:PVDF = 95:3:2 (by weight). A current collector coated with [the specified substance] was used. NMP was used as the solvent for the slurry.
[0486] After coating the current collector with slurry, the solvent was evaporated. Then, pressurization was applied at 210 kN / m. After that, further pressurization was applied at 1467 kN / m. Through the above process, the positive electrode was obtained. The load on the electrode is approximately 7 mg / cm³. 2 That's what I decided.
[0487] Using the fabricated positive electrode, a CR2032 type (20mm diameter, 3.2mm height) coin was used. A rechargeable battery of type [type] was manufactured.
[0488] Lithium metal was used for the counter electrode.
[0489] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluoride phosphate (LiPF6). The electrolyte used is ethylene carbonate (EC) and diethyl carbonate (DEC). A mixture with an EC:DEC ratio of 3:7 (by volume) was used. The cycle characteristics were evaluated as follows: For the rated secondary batteries, 2 wt% vinylene carbonate (VC) was added to the electrolyte. did.
[0490] A 25 μm thick polypropylene was used for the separator.
[0491] The positive electrode and negative electrode cans were made of stainless steel (SUS).
[0492] <Cycle Characteristics> Next, the cycle characteristics of the fabricated secondary battery were evaluated. At 25°C, charging... The discharge is CCCV (0.5C, 4.6V, cutoff current 0.05C), and the discharge is CC (0.5C, 2. The cycle characteristics were evaluated by repeatedly charging and discharging the battery at 5V.
[0493] The cycle characteristics after 50 cycles are shown in Figures 34 to 36. The horizontal axis represents the discharge capacity maintenance. The vertical axis represents the rate, and the vertical axis represents the discharge energy. Figures 34, 35, and 36 show magnesium The values of 0.5, 1.0, and 2.0 are summarized when the amount of cobalt is set to 100. Table 2 also shows the discharge capacity retention rate after 50 cycles when the amount of magnesium is 2.0. Table 3 shows the discharge energy for each.
[0494] [Table 2]
[0495] [Table 3]
[0496] Figure 37 shows two conditions where both nickel and aluminum are set to 0.25 or 0.5. , and without performing steps S41 to S44, add nickel and aluminum Maintaining discharge capacity under conditions where none existed (indicated as "Ni: -, Al: -" in the legend of the figure). The rates and discharge energy are shown in excerpts.
[0497] Each clause specifies that the nickel content is greater than 0.1 and less than 1, and the aluminum content is 0.1 or more and less than 1. In this case, superior properties were obtained. Furthermore, particularly excellent properties were obtained under the condition of a magnesium content of 1. Sex was obtained.
[0498] <Continuous charging endurance> Next, if we consider the number of cobalt atoms to be 100, then consider the number of magnesium atoms to be 1.0 or 1 0.5, and the number of nickel and aluminum atoms is either none or 0.25. The active material was prepared, a secondary battery was fabricated using the method described above, and the continuous charge endurance was evaluated. Ta.
[0499] Each secondary battery using the fabricated positive electrode active material underwent a single charge-discharge cycle at 25°C. Charging will be performed using CCCV (0.2C, 4.5V, cutoff current 0.02C), followed by a 2-minute pause after charging. A time limit was set. Discharge was performed at CC (0.2C, 3.0V), and a 2-minute rest period was set after discharge. Ta.
[0500] Subsequently, continuous charging was performed at 60°C using CCCV (0.5C). Upper voltage limit The voltage was set to 4.6V. 1C was set to 191.7mA / g.
[0501] If the number of magnesium atoms is set to 1.0 compared to the number of cobalt atoms which is 100, The result when the value is set to 1.5 is shown in Figure 38A, and the result when the value is set to 1.5 is shown in Figure 38B.
[0502] Excellent continuous resistance was obtained under conditions where nickel and aluminum were added.
[0503] <xps> When the number of atoms in cobalt is set to 100, magnesium, nickel, and aluminum The amount of each of the four conditions (XPS-1 to XPS-4) shown in Table 4 should be as described above. The cathode active material was prepared according to the method and then subjected to XPS analysis.
[0504] [Table 4]
[0505] Table 5 shows the concentrations of each element obtained by XPS.
[0506] [Table 5]
[0507] Even under conditions where nickel was added, XPS analysis showed results below the detection limit. Aluminum was detected under conditions where aluminum was added. Even in this case, the value was lower than one-quarter of the amount of magnesium. From this, for example, Aluminum may diffuse more easily into particles than magnesium, and also, aluminum Nickel may diffuse more easily into particles than um.
[0508] <XRD on the positive electrode> Among the obtained positive electrode active materials, the number of atoms of magnesium, nickel, and aluminum is Positive electrodes were fabricated using positive electrode active materials under conditions of 1, 0.5, and 0.5, respectively.
[0509] For this positive electrode, after one charge / discharge cycle to check its capacity, check the voltage at 4.5V, 4.55V, or 4 The device was charged at 0.6V and XRD analysis was performed.
[0510] For capacity verification charging, use CCCV (0.2C, 4.5V, cutoff current 0.05C), and after charging 2 A 0-minute rest period was provided. Discharge was performed at CC (0.2C, 3V), and a 20-minute rest period was provided after discharge. A test was set up. The temperature was 25°C, and 1C = 191mA / g.
[0511] Subsequent charging at 4.5V, 4.55V, or 4.6V is CCCV (0.2C, each voltage) The termination current was set to 0.02C. After charging, the secondary battery was stored in a glove box under an argon atmosphere. The device was disassembled, the positive electrode was removed, and cleaned with DMC. Afterward, it was sealed in an argon atmosphere. The samples were sealed in containers and subjected to XRD analysis. Figures 39 and 40 show the XRD results. Figure 39 Figures 40 and 40 show different ranges for the horizontal axis of 2θ.
[0512] The lattice constants were determined from the obtained XRD results, and the charging voltages were 4.5V and 4.55V. At 4.6V, the a-axis is 2.812, 2.814, and 2.818 respectively [× 10 -10 m], and the c-axis is 14.28, 14.04 and 13.79 [×10 -10 It was m]. [Examples]
[0513] Next, a secondary battery was fabricated using a different composite oxide material than that used in Example 1.
[0514] <Secondary Battery Fabrication 2> As the composite oxide used in step S24, MTI's EQ-Lib-LCO is used for positive We prepared the most active material.
[0515] The manufacturing conditions are the following five conditions. The first is steps S11 to S13 and step Without performing steps S21 to S24, magnesium, nickel, and aluminum These are the conditions that were not added (indicated as "Mg:-,Ni:-,Al:-" in Figure 42). For example, if the number of atoms in cobalt is 100, the number of atoms in magnesium is 1.0, and nickel This is the condition where no iron or aluminum was added (Mg:1, Ni:-, Al:-). 3 The claw is calculated by setting the number of magnesium atoms to 1.0 when the number of cobalt atoms is 100, and nickel Under conditions where the atomic number of both ru and aluminum is 0.25 (Mg:1, Ni:0.25, Al: 0.25). The fourth is that when the number of cobalt atoms is set to 100, the amount of magnesium Under the condition where the number of atoms is set to 1.0 and the number of atoms of nickel and aluminum are both 0.5 (M (g:1, Ni:0.5, Al:0.5). The fifth is with 100 cobalt atoms. When the number of atoms of magnesium, nickel, and aluminum is all set to 1.0, the conditions are (M The conditions are g:1, Ni:1, Al:1). A secondary battery was fabricated using the method described in Example 1, and its cycle characteristics were evaluated. The amount of battery loaded was approximately 7 m³. g / cm 2 The positive electrode is approximately 20 mg / cm³. 2 Two types of positive electrodes were prepared. The test temperature was set to 45°C, and the maximum charging voltage was set to 4.6V.
[0516] <Cycle Characteristics> Figure 41 shows the measurement results of the particle size distribution of the MTI composite oxide used. Also, the supported amount was approximately 7 mg / cm 2 Figure 42 shows the results of the positive electrode cycle characteristics, with a loading amount of approximately 20 mg / cm³. 2 and Figure 43 shows the cycle characteristics of the positive electrode. The addition of magnesium improved the cycle characteristics. This was observed, and further improvements were seen with the addition of nickel and aluminum.
[0517] <Making a secondary battery 3> In step S24, lithium cobalt oxide manufactured by Aldrich is used as the composite oxide. The positive electrode active material was then prepared. The preparation conditions were as follows: The first is step S11 Without performing steps S13 and S21 to S24, magnesium, The first condition is without adding cobalt and aluminum. The second is with 10 cobalt atoms. When the value is set to 0, the number of magnesium atoms is set to 0.5, and nickel and aluminum are added. These conditions were not present. For the positive electrode active material prepared under these conditions, refer to the method in Example 1. A secondary battery was fabricated, and its cycle characteristics were evaluated. The cycle test temperature was 45°C, and the charge was charged. The upper limit voltage of the electric current was set to 4.55V.
[0518] <Cycle Characteristics> Figure 44 shows the measurement results of the particle size distribution of the Aldrich composite oxide used. The results of the cycle characteristics are shown in Figure 45. Improvements in cycle characteristics were observed with the addition of magnesium. Ta. [Examples]
[0519] In this example, the characteristics of a secondary battery using a positive electrode active material according to one embodiment of the present invention were evaluated.
[0520] <Fabrication of positive electrode active material> The cathode active material was prepared by referring to the flow chart in Figure 10.
[0521] First, a mixture containing magnesium and fluorine is prepared by steps S11 to S13. I prepared substance 902. The molar ratio of LiF to MgF2 is LiF:MgF2=1:3. The weighed LiF and MgF2 were dry-ground and mixed. This was performed using a ball mill with zirconia balls at 150 rpm for 1 hour. The materials were recovered and designated as mixture 902.
[0522] Next, as a composite oxide, Cellseed 5H manufactured by Nippon Chemical Industrial Co., Ltd. was prepared (step (P S24). The particle size distribution results for 5H are shown in Figure 47.
[0523] Next, mixture 902 and the composite oxide were mixed (step S31). If the number of cobalt atoms is set to 100, then the number of magnesium atoms in mixture 902 The weights were weighed so that the number was 0.5 or 2. The mixture was dry-mixed. The mixture was zirconia. The process was carried out using a ball mill with balls at 150 rpm for 1 hour. For comparison, We also created a test condition without adding magnesium.
[0524] Next, the processed material was recovered to obtain mixture 903 (step S32).
[0525] Next, the mixture 903 is placed in an alumina crucible and heated in an oxygen atmosphere muffle furnace at 850°C, 6 The material was annealed for 0 hours (step S33). During annealing, the alumina crucible was covered. The oxygen flow rate was set to 10 L / min. The heating rate was set to 200°C / hr, and the cooling rate was set to 10 hours or more. The process was carried out. The material after heat treatment was collected and sieved to obtain a second composite oxide (S Step S34).
[0526] Next, nickel hydroxide, the metal source, and the second composite oxide were ball-milled together. When the number of cobalt atoms is set to 100, the number of nickel atoms is set to 0.5. The mixture was mixed. The mixing was performed using a ball mill with zirconia balls at 150 rpm for 1 hour. After mixing, the mixture was passed through a 300 μm diameter sieve. Then, the resulting mixture was subjected to an alumina crucible. It was placed in a container, covered, and annealed at 850°C for 2 hours in an oxygen atmosphere.
[0527] Next, a coating layer containing aluminum was formed by the sol-gel method. A was used as the metal source. Isopropoxide was used, and 2-propanol was used as the solvent. Number of cobalt atoms When the total is set to 100, the mixture was prepared so that the number of aluminum atoms was 0.5. After that, The mixture is placed in an alumina crucible, covered, and incubated at 850°C for 2 hours in an oxygen atmosphere. The mixture was then passed through a 53 μm diameter sieve to recover the powder and obtain the positive electrode active material.
[0528] <Manufacturing of secondary batteries> Using the positive electrode active materials obtained above, each positive electrode was fabricated. As a comparative example, Celsi A positive electrode using 5H as the positive electrode active material (in Figure 48, Mg:-, Ni:-, Al: (as stated) was also manufactured. The positive electrode active material was AB and PVDF, with active material:AB:PVDF=9 A slurry mixed in a 5:3:2 (weight ratio) was used and coated onto the current collector. NMP was used as the solvent.
[0529] After coating the current collector with slurry, the solvent was evaporated. Then, pressurization was applied at 210 kN / m. After that, further pressurization was applied at 1467 kN / m. Through the above process, the positive electrode was obtained. The load on the electrode is approximately 7 mg / cm³. 2 That's what I decided.
[0530] Using the fabricated positive electrode, a CR2032 type (20mm diameter, 3.2mm height) coin was used. A rechargeable battery of type [type] was manufactured.
[0531] Lithium metal was used for the counter electrode.
[0532] The electrolyte in the electrolyte solution contains 1 mol / L lithium hexafluoride phosphate (LiPF6). The electrolyte used is ethylene carbonate (EC) and diethyl carbonate (DEC). A mixture with an EC:DEC ratio of 3:7 (by volume) was used. The cycle characteristics were evaluated as follows: For the rated secondary batteries, 2 wt% vinylene carbonate (VC) was added to the electrolyte. did.
[0533] A 25 μm thick polypropylene was used for the separator.
[0534] The positive electrode and negative electrode cans were made of stainless steel (SUS).
[0535] <Cycle Characteristics> Next, the cycle characteristics of the fabricated secondary battery were evaluated at 45°C. After charging and discharging three times to confirm the battery capacity, it was charged and discharged 50 times for a cycle test.
[0536] For capacity verification charging, use CCCV (0.2C, 4.5V, cutoff current 0.02C), and after charging... A 20-minute rest period was provided. Discharge was performed using CV (0.2C, 3V), and a 20-minute rest period was provided after discharge. It was established.
[0537] The charging for the cycle test will be CCCV (0.76C, 4.6V, cutoff current 0.02C). A 20-minute rest period was included after charging. Discharging was performed using CV (0.76C, 3V), followed by a 20-minute rest period. A time limit was set. Also, 1C = 177.5mA / g was used.
[0538] The cycle characteristics are shown in Figure 48. By adding nickel and aluminum... A significant improvement in cycle characteristics was observed. Furthermore, the discharge capacity value varied depending on the amount of magnesium added. A difference was observed, and superior discharge capacity was obtained under the condition of magnesium at 0.5. [Explanation of symbols]
[0539] 100: Positive electrode active material, 101: Particles, 102: Particles, 103: Coating, 108: Current collector, 1 09: Positive electrode active material layer, 111: Region, 112: Region< / xps> < / xrd> < / edx> < / xps>
Claims
1. A lithium-ion secondary battery having a positive electrode and a negative electrode, The aforementioned negative electrode has a negative electrode active material containing carbon, The positive electrode has a positive electrode active material, The positive electrode active material has particles containing cobalt, oxygen, and aluminum. The positive electrode active material has a crystalline structure having a space group of R-3m, The aforementioned crystal structure was estimated by Rietveld analysis of the pattern obtained by powder X-ray diffraction. When EDX analysis is performed on the cross-section of the aforementioned particles, The particle has a first region at a distance of 20 nm or more and 200 nm or less from the surface, and in the first region, the number of aluminum atoms in the EDX analysis is 0.04 times or more and less than 1.6 times the number of cobalt atoms. A lithium-ion secondary battery having a second region at a distance of 1 μm or more and 3 μm or less from the surface of the particles, wherein in the second region, the number of aluminum atoms in the EDX analysis is less than 0.03 times the number of cobalt atoms.
2. A lithium-ion secondary battery having a positive electrode and a negative electrode, The negative electrode has a negative electrode active material containing silicon, The positive electrode has a positive electrode active material, The positive electrode active material has particles containing cobalt, oxygen, and aluminum. The positive electrode active material has a crystalline structure having a space group of R-3m, The aforementioned crystal structure was estimated by Rietveld analysis of the pattern obtained by powder X-ray diffraction. When EDX analysis is performed on the cross-section of the aforementioned particles, The particle has a first region at a distance of 20 nm or more and 200 nm or less from the surface, and in the first region, the number of aluminum atoms in the EDX analysis is 0.04 times or more and less than 1.6 times the number of cobalt atoms. A lithium-ion secondary battery having a second region at a distance of 1 μm or more and 3 μm or less from the surface of the particles, wherein in the second region, the number of aluminum atoms in the EDX analysis is less than 0.03 times the number of cobalt atoms.
3. In claim 1 or claim 2, The cross-section of the aforementioned particle is exposed by processing using a focused ion beam processing and observation device, in a lithium-ion secondary battery.
4. A lithium-ion secondary battery having a positive electrode and a negative electrode, The aforementioned negative electrode has a negative electrode active material containing carbon, The positive electrode has a positive electrode active material, The positive electrode active material has particles containing cobalt, oxygen, nickel, and aluminum. When the pattern obtained by powder X-ray diffraction of the positive electrode active material is subjected to Rietveld analysis, it is found to have a crystalline structure with a space group of R-3m. When EDX analysis is performed on the cross-section of the aforementioned particles, The particle has a first region at a distance of 20 nm or more and 200 nm or less from the surface, and in the first region, the number of aluminum atoms in the EDX analysis is 0.04 times or more and less than 1.6 times the number of cobalt atoms. A lithium-ion secondary battery having a second region at a distance of 1 μm or more and 3 μm or less from the surface of the particles, wherein in the second region, the number of aluminum atoms in the EDX analysis is less than 0.03 times the number of cobalt atoms.
5. A lithium-ion secondary battery having a positive electrode and a negative electrode, The negative electrode has a negative electrode active material containing silicon, The positive electrode has a positive electrode active material, The positive electrode active material has particles containing cobalt, oxygen, nickel, and aluminum. When the pattern obtained by powder X-ray diffraction of the positive electrode active material is subjected to Rietveld analysis, it is found to have a crystalline structure with a space group of R-3m. When EDX analysis is performed on the cross-section of the aforementioned particles, The particle has a first region at a distance of 20 nm or more and 200 nm or less from the surface, and in the first region, the number of aluminum atoms in the EDX analysis is 0.04 times or more and less than 1.6 times the number of cobalt atoms. A lithium-ion secondary battery having a second region at a distance of 1 μm or more and 3 μm or less from the surface of the particles, wherein in the second region, the number of aluminum atoms in the EDX analysis is less than 0.03 times the number of cobalt atoms.
6. In claim 4 or claim 5, A lithium-ion secondary battery in which, in the first region, the number of nickel atoms in the EDX analysis is less than 0.5 times the number of aluminum atoms.
7. In any one of claims 4 to 6, The cross-section of the aforementioned particle is exposed by processing using a focused ion beam processing and observation device, in a lithium-ion secondary battery.
8. In any one of claims 1 to 7, The positive electrode active material is a lithium-ion secondary battery in which the number of sulfur atoms, as measured by glow discharge mass spectrometry, is 150 ppm wt or more and 2000 ppm wt or less.
9. In any one of claims 1 to 8, The positive electrode active material is a lithium-ion secondary battery in which the number of titanium atoms, as measured by glow discharge mass spectrometry, is 300 ppm wt or less.
Citation Information
Patent Citations
Positive active material for lithium secondary battery
JP2001291518A
Positive electrode active material for lithium secondary battery and method for manufacturing the same
JP2002216760A
Positive electrode active material for lithium secondary battery
JP2003217572A
Positive electrode active material for lithium secondary battery and its manufacturing method
JP2006261132A
Positive electrode material for nonaqueous secondary batteries, manufacturing method thereof, positive electrode mixture layer for nonaqueous secondary batteries arranged by use of positive electrode material for nonaqueous secondary batteries, positive electrode for nonaqueous secondary batteries, and nonaqueous secondary battery
JP2015069958A